Land-use optimization to support cost-effective landscape transformation policies for wildfire mitigation - Rui Serôdio Simões; Paulo Flores Ribeiro; Marta Mesquita; Isabel Martins; João Morais Mourato; José Lima Santos (Ecological Economics, 2026)

Salience Network Dynamics Across Spontaneous Attacks, Interictal Rest and Interictal Pain Imagery in Menstrually Related Migraine - Inês Esteves; Alexandre Perdigão; Ana R. Fouto; Amparo Ruiz-Tagle; Gina Caetano; Joana Cabral; Isabel Pavão Martins; Raquel Gil-Gouveia; César Caballero-Gaudes; Patrícia Figueiredo (Brain Topography, 2026)

Removal of emerging organic pollutants from soil medium with engineered nanomaterials – Advances and future prospects - Mohammadreza Khalaj; Mohammadreza Kamali; Rahim Molaey; Tejraj M. Aminabhavi; Luísa Margarida Martins; M. Elisabete V. Costa; Isabel Capela; Raf Dewil (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Exploratory short-term forecasting of respiratory hospital admissions in lisbon using air-quality and meteorological data - Behrouz Nemati; Bárbara T. Silva; Farzaneh Abedian Aval; Sina Ataee; Diogo Lopes; Vânia Martins; Ana Isabel Miranda; Hélder Relvas (Atmospheric Pollution Research, 2026)

Halogenated bisphenol A alternatives inhibit aldo-keto reductase 1C1 and induce metabolic alterations in human adipocytes - Jasmin Kleißen; Cornelius Goerdeler; Alix Sarah Aldehoff; Isabel Karkossa; Anna Didio; Johannes Schmidt; Stefan Kalkhof; Jörg Lehmann; Ulrike Rolle-Kampczyk; Marina Grimaldi; Patrick Balaguer; Maximilian Faissner; et al. (Journal of Hazardous Materials, 2026)

Genomic structure and environmental adaptation in northern red oak: Foundations for climate-resilient forestry - Lisa Tischenko; Nathalie Isabel; Lyne Touchette; Éric Normandeau; Brian Boyle; Martin Williams; Charalambos Neophytou; Simon Jansen; Mirko Liesebach; Antoine Kremer; John J. MacKay; André Rainville; et al. (Forest Ecology and Management, 2026)

Treatment with Alamandine Reduces Established Pulmonary Fibrosis: Preliminary Histological, Functional, and Biochemical Insights - Isabel Amaral Martins; Andresa Thomé Silveira; Juliane Flor; Aline Blanco; Giuliano Rizzotto Guimarães; Adriana Fernanda K. Vizuete; Katya Rigatto (International Journal of Peptide Research and Therapeutics, 2026)
Introduction Pulmonary fibrosis (PF) is a challenging interstitial lung disease with limited therapeutic options. This study explores the therapeutic effects of alamandine (ALA), a renin-angiotensin system peptide, in reversing established fibrotic progression in an experimental model. Methods Male Wistar rats were divided into four groups ( n = 5–6/group): control (CO), ALA-treated (ALA), bleomycin-induced fibrosis (BLM), and bleomycin plus ALA treatment (BA). Fibrosis was induced by intratracheal bleomycin (2.5 mg/kg) on day 0. Subcutaneous ALA treatment (50 µg/kg/day) began on day 10 and continued until day 19. Respiratory mechanics, body weight, Ashcroft score, and lung transforming growth factor-beta (TGF-β) content were evaluated. Plasma RAS peptides were quantified by LC-MS/MS. Results Bleomycin significantly increased respiratory resistance (CO = 0.104 ± 0.026 vs. BLM = 0.159 ± 0.047 cmH₂O.s/mL in CO, p < 0.008) and Ashcroft score, and reduced body weight gain. ALA treatment from day 10–20 markedly improved body weight gain ( p < 0.001), reduced Ashcroft score (BLM = 2.23 ± 0.35 vs. BA = 1.21 ± 0.40, p < 0.0001), and decreased lung TGF-β1 content (BLM = 3.70 ± 1.7 vs. BA = 1.10 ± 0.42 pg/mg protein, p < 0.0015). These results were associated with qualitatively improved respiratory effort, suggesting attenuation of bleomycin-induced fibrogenesis. Conclusion Despite rapid tissue uptake, late ALA treatment was associated with reduced histological fibrosis, lower TGF-β1 content, and improved selected functional and clinical indicators in rats with established pulmonary fibrosis. These findings suggest a potential therapeutic benefit that warrants further dose- and time-ranging studies.

Marine migration influences mercury accumulation in anadromous Arctic char ( Salvelinus alpinus ) - Isabel R. Hilgendag; Michael Power; Mehdi M. Aqdam; Christopher W. Lewis; Zoya Martin; Ashley D. Ehrman; Heidi K. Swanson (Journal of Fish Biology, 2026)
Mercury (Hg) is a globally distributed toxic metal present in northern natural environments that biomagnifies in food webs and bioaccumulates in apex predator fish, such as Arctic char ( Salvelinus alpinus )—an iteroparous species with a circumpolar distribution. Arctic char exhibit a variety of life history types, with the migrating, anadromous life‐history type supporting many subsistence and small‐scale commercial fisheries in the Arctic and sub‐Arctic. Despite anadromous Arctic char having generally lower Hg concentrations than non‐anadromous conspecifics, the mechanisms that contribute to significant inter‐individual differences within this life‐history group have not been well investigated. A total of 119 anadromous Arctic char were captured from inner Frobisher Bay on Baffin Island near Iqaluit, Nunavut, in 2018 and 2019, to investigate causes of inter‐individual differences in Hg concentrations in the anadromous life‐history type of Arctic char. As hypothesized, Hg concentrations significantly decreased with increasing marine prey reliance; marine prey reliance—quantified using δ 34 S ratios—explained 93% of the variability in Hg. Arctic char that relied more on marine (vs freshwater) prey had lower Hg concentrations. Delta 34 S ratios and average somatic growth rate (size‐at‐age) were the best predictors of Hg concentrations among the set of biological variables assessed, and both were negatively related to Hg concentrations in common age groups (i.e., ages 9–13). For samples that had migration data available, Hg concentration increased with age‐at‐first migration ( R 2 = 0.32) and decreased with number of marine migrations ( R 2 = 0.57), suggesting that plasticity in life history tactics affects Hg concentrations in anadromous Arctic char. Overall, results indicate that differences in habitat use and feeding environment (i.e., freshwater vs. marine) play a significant role in determining Hg bioaccumulation in anadromous Arctic char.

Plinia peruviana (Poir.) Govaerts (jabuticaba) extract inhibits the development of gastric ulcers in animal models through gastroprotective mechanisms - Isabel Sousa Alcântara; Renata Torres Pessoa; Lucas Yure Santos da Silva; Roger Henrique Souza da Costa; Aparecida Barros da Silva; Tarcisio Mendes Silva; Samara Alves Brito; Anita Oliveira Brito Pereira Bezerra Martins; Jean Carlos Pereira Sousa; Andréa Rodrigues Chaves; Ricardo Neves Marreto; Francisco Sandro Menezes Rodrigues; et al. (Food Bioscience, 2026)

Scientific trends on agroforestry and climate change: a scientometric analysis (2014–2024) - Elen Raquel Ferreira Maciel; Françóyse Dávilla de Souza Silva; Maria Cecília Costa Godeiro; Maria Isabel Souza de Lucena; Stefany Caroliny de Souza Rocha; Antonia Gilvanira da Silva; Fernanda Ramos de Medeiros; Francisco Edvar Lima Júnior; Darliane Cristina Soares de Souza; Eulene Francisco da Silva; Carolina Malala Martins Souza; Daniel Valadão Silva; et al. (Agroforestry Systems, 2026)

Development of a Community-engaged Research Training Workshop for Clinician-Scientists and Early-stage Investigators - Emily P. Courtney; Cathy D. Meade; Clement K. Gwede; Veronica Barrios-Monroy; Isabel C. Scarinci; Usha Menon; Monica Baskin; David Schwartz; Monica E. Peek; Anissa I. Vines; Z’Kera Peoples; Jamboor K Vishwanatha; et al. (Journal of Cancer Education, 2026)
Community-engaged research (CEnR), a collaboration between academics and community partners, is an effective approach in addressing the social drivers of health (SDOH) and health disparities in local communities. Yet, CEnR training is often not a standard component of training programs in research or clinical programs. To meet the need for CEnR training, we developed and implemented a workshop to increase CEnR knowledge and skills among clinician-scientists and early-stage investigators (ESIs), and create opportunities for ongoing mentorship and professional development. In this manuscript, we discuss the organization of this workshop, learning objectives, supporting activities, and follow-up methods to facilitate a successful and engaging training experience. The workshop was developed through collaborative efforts with experts in CEnR, Community-Based Participatory Research (CBPR), cancer disparities, and SDOH. The workshop focused on (1) an introduction to CEnR and the opportunity for attendees to develop their own CEnR research ideas; (2) varied presentations, interactive activities, experiential learning, and discussion topics to fulfill the workshop’s learning objectives; (3) year-long opportunities for professional development and continued mentorship; and (4) evaluations of the workshop. Twenty-four ESIs and 11 clinician-scientists participated in the workshop. Using survey methods and descriptive statistics, the workshop was evaluated positively by participants. This manuscript provides guidance for both in-person and virtual workshop formats, from inception to implementation, and recommendations for other workshop facilitators. The impact of these workshops has the potential to have positive downstream implications for community-engaged research.

Co-evolution of marine ecosystems and nutrient cycles during the Great Ordovician Biodiversification Event - Shengchao Yang; Thomas J. Algeo; Thomas Servais; Ronald E. Martin; David A.T. Harper; Charles R. Marshall; Yiying Deng; Zongyuan Sun; Zhengbo Lu; Jian Cao; Chao Li; Shu-zhong Shen; et al. (Earth and Planetary Science Letters, 2026)

Caffeine removal and degradation in sanitary sewage: Insights into microbial shifts and methane yield - Rômulo Mota Teixeira; Caroline Varella Rodrigues; Carolina Nemeth Comparato; Eduardo Lordelo Volpato; Guilherme Martins Grosseli; Isabel Kimiko Sakamoto; Maria Bernadete Amâncio Varesche (Journal of Water Process Engineering, 2026)

Role of anaerobic digestion in removing antibiotic resistance agents from Brazilian and Spanish sewage sludge - Eliane Cristina Braga Martins Gonçalves; Andressa Rezende Pereira; Jéssica Aparecida de Bessa Cabral; Aline Gomes de Oliveira Paranhos; Carla Valencia Berzosa; Israel Díaz; Sara Isabel Pérez-Elvira; Silvana de Queiróz Silva; Sérgio Francisco de Aquino (Journal of Environmental Chemical Engineering, 2026)

Design and validation of an SNP-based assay for detecting Juglans ailantifolia introgression into Juglans cinerea populations or living collections - Martin Williams; Manuel Lamothe; Aziz Ebrahimi; Berni M. van der Meer; Mojtaba Zamani Faradonbeh; Anna O. Conrad; James Warren; Carolyn C. Pike; Douglass F. Jacobs; Nathalie Isabel (Tree Genetics & Genomes, 2026)
Butternut ( Juglans cinerea L.) is a rapidly declining tree species threatened by Ophiognomonia clavigignenti-juglandacearum (Oc-j), the causal agent of butternut canker. The introduction of Japanese walnut ( Juglans ailantifolia Carrière), which hybridizes with butternut and exhibits greater resistance to the disease, presents both a conservation challenge and a potential avenue for genetic improvement. Identifying non-admixed butternuts is critical for conservation efforts and breeding programs aimed at preserving the species’ genetic integrity while exploring resistance strategies. However, morphological identification of first and advanced generation hybrids is unreliable, necessitating the development of efficient detection tools. In this study, we developed and validated a cost-effective, high-throughput SNP genotyping tool using the MassARRAY platform to distinguish between J. cinerea , J. ailantifolia , and their hybrids. The panel consists of 28 nuclear SNPs and two chloroplast SNPs and demonstrates strong concordance with genotyping-by-sequencing (GBS) results using nearly 12,000 SNPs (R² = 0.98), indicating high predictive accuracy. Field testing this genotyping tool to 1,269 trees from natural stands and breeding programs in Canada and the U.S. revealed substantial hybridization, particularly in U.S. plantations, where hybrids comprised up to 18% of tested trees. Chloroplast analysis confirmed asymmetrical hybridization patterns, with J. ailantifolia acting predominantly as the maternal parent. This SNP panel provides a valuable tool for conservation, breeding, and regulatory applications by enabling rapid and accurate hybrid identification. Its implementation will help guide recovery strategies for butternut, ensuring that conservation efforts are informed by precise genetic data.

A Single Amino Acid Substitution in CspA Increases Germination Sensitivity and Broadens Bile Salt Germinant Specificity in Clostridioides difficile Spores - Isabel Roseiro; Alexandra Nunes; Diogo Martins; Frederico Alves; Søren Persson; Adriano O. Henriques; Mónica Oleastro; Mónica Serrano (Environmental Microbiology, 2026)
Once regarded primarily as a healthcare‐associated pathogen, Clostridioides difficile has increasingly been reported as a cause of community‐acquired infection, raising questions about the contribution of animal and environmental reservoirs to persistence and transmission. Ribotype 033 (RT033) is predominantly associated with animal and environmental reservoirs, yet key traits underlying its ecology are poorly defined. Here we show that RT033 strains produce spores with enhanced germination sensitivity and expanded germinant specificity, enabling germination at low concentrations of bile‐salts and in response to bile‐salts that are typically inhibitory, including those more typical of animal hosts. Genetic analysis identified a single amino acid substitution (R1036I) in CspA, a component of the CspBAC germination apparatus, as the determinant of this phenotype. Expression of the RT033 cspBAC operon in a laboratory strain was sufficient to confer increased sensitivity and expanded bile‐salt responsiveness. The R1036I substitution disrupts a conserved salt bridge at the CspA:CspC interface while not causing major destabilisation of the complex in the absence or presence of germinants and co‐germinants. Together, our findings reveal a naturally occurring rewiring of bile‐salt sensing in spores of RT033 strains that likely reflects adaptation to animal‐associated bile‐acid environments and may influence persistence, transmission, and zoonotic potential of this lineage.

Dispersion and potential impacts of a white wave of pellets after an accident off NW Iberian Peninsula - Martinho Marta-Almeida; Irene Martins; Alexandra Guerra; Miguel M. Santos; Isabel Iglesias; Fabiola N. Amorim (Journal of Marine Systems, 2026)

Comparing different food banks: A case study application of a proposed standard - Martin Johannes du Plessis; Euodia Vermeulen; Helmut Aschbacher; Sara Grobbelaar; Isabel Meyer (Global Food Security, 2026)

Roles of base and nucleotide excision repair activities in cancer treatment: implications for prognosis and resistance to therapy in breast and colorectal cancers - Ana Rita Guedes; Carlos Martins-Gomes; Renato Cunha; Amélia M. Silva; Isabel Gaivão (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2026)

Iron-exchanged Y-type zeolites for phosphorus recovery from eutrophic waters: Kinetics and performance in real lake matrix - Anna C.M. Martins; Jéssica T. Santos; Teresa Tavares; António G. Brito; António M. Fonseca; Isabel C. Neves; Gilberto Martins (Journal of Environmental Chemical Engineering, 2026)

Are all nanoplastics equally neurotoxic? Influence of size and surface functionalization on the toxicity of polystyrene nanoplastics in human neuronal cells - Carolina Mota; Ana Margarida Araújo; Maria Enea; Eulália Pereira; Ana Reis-Mendes; Rui Fernandes; Sofia Pacheco; Marlene Lúcio; Carla Martins Lopes; Isabel M.P.L.V.O. Ferreira; Márcia Carvalho (Environmental Pollution, 2026)

Molecular phylogeny reveals new morphological and ecological insights into the Cyperus margaritaceus–niveus complex - Martin Xanthos; George Burton; Lisa Pokorny; Alice Merrall; Isabel Larridon (Plant Systematics and Evolution, 2026)
The Cyperus margaritaceus–niveus complex (Cyperaceae) is a group of nine C4 Cyperus species ( C. karlschumanii , C. kibweanus , C. ledermannii , C. margaritaceus , C. nduru, C. niveus var. leucocephalus , C. somaliensis , C. sphaerocephalus , and C. tisserantii ) from Sub-Saharan Africa and Madagascar united by the combination of a capitate inflorescence, white–yellow glumes and swollen bulb-like bases. Previous molecular studies hinted that this complex forms a natural group within the C4 Cyperus Clade, although not all taxa were included. In this study, we used the Angiosperms353 bait kit to generate sequence data for all taxa in the complex. The species complex was resolved as monophyletic, while inter-species relationships produced differing results. Cyperus sphaerocephalus , C. kibweanus , C. ledermannii , C. somaliensis , and C. tisserantii were resolved as monophyletic, while C. karlschumannii appears monophyletic except for a moderately resolved isolated lineage that is positioned elsewhere. Cyperus niveus var. leucoephalus was resolved as paraphyletic. Cyperus nduru was resolved as polyphyletic even after rechecking determinations of the specimens. The latter result appears to show correlation with habitat in which one clade comprises specimens associated with Miombo woodland and another clade that comprising specimens associated with bowal grassland. This ecological difference correlates with differences in underground organ morphology. Cyperus margaritaceus requires further study to delimit since a specimen identified as this species is found in an unusual position in the phylogeny, possibly representing a new species to science. Combining this phylogenomic dataset with previous studies on morphometrics demonstrates how such integrative and iterative taxonomic methods can be the optimal approach in resolving species complexes in species-rich genera such as Cyperus , especially in the rapid diversifying C4 Cyperus Clade.

Correction: Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)

Vulnerability of marine megafauna to global at‐sea anthropogenic threats - Michelle VanCompernolle; Juliet Morris; Hannah J. Calich; Jorge P. Rodríguez; Sarah A. Marley; Jessica R. Pearce; Briana Abrahms; Katya Abrantes; André S. Afonso; Alex Aguilar; Andrews Agyekumhene; Tomonari Akamatsu; et al. (Conservation Biology, 2026)
Marine megafauna species are affected by a wide range of anthropogenic threats. To evaluate the risk of such threats, species’ vulnerability to each threat must first be determined. We build on the existing threats classification scheme and ranking system of the International Union for Conservation of Nature (IUCN) Red List of Threatened Species by assessing the vulnerability of 256 marine megafauna species to 23 at‐sea threats. The threats we considered included individual fishing gear types, climate‐change‐related subthreats not previously assessed, and threats associated with coastal impacts and maritime disturbances. Our ratings resulted in 70 species having high vulnerability ( v > 0.778 out of 1) to at least 1 threat, primarily drifting longlines, temperature extremes, or fixed gear. These 3 threats were also considered to have the most severe effects (i.e., steepest population declines). Overall, temperature extremes and plastics and other solid waste were rated as affecting the largest proportion of populations. Penguins, pinnipeds, and polar bears had the highest vulnerability to temperature extremes. Bony fishes had the highest vulnerability to drifting longlines and plastics and other solid waste; pelagic cetaceans to 4 maritime disturbance threats; elasmobranchs to 5 fishing threats; and flying birds to drifting longlines and 2 maritime disturbance threats. Sirenians and turtles had the highest vulnerability to at least one threat from all 4 categories. Despite not necessarily having severe effects for most taxonomic groups, temperature extremes were rated among the top threats for all taxa except bony fishes. The vulnerability scores we provide are an important first step in estimating the risk of threats to marine megafauna. Importantly, they help differentiate scope from severity, which is key to identifying threats that should be prioritized for mitigation.

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

ProAKAP4 as a protein marker of sperm quality: Insights from frozen-thawed ejaculated and epididymal sperm - Myrian Megumy Tsunokawa Hidalgo; Ana Beatriz Marques de Almeida; Leticia Amanda dos Santos Silva; Vinicius Wagner Silva; Julia Rodrigues Greghi; Natália Ribeiro Sambatti; Luiz Guilherme Corsi Trautwein; Rodrigo Yudi Palhaci Marubayashi; João Carlos Pinheiro Ferreira; Maria Isabel Mello Martins (Theriogenology, 2026)

Functional diversity of Brazilian bees: revealing the unique patterns of the Neotropics - Guaraci D. Cordeiro; Tereza C. Giannini; Patrick M. Consorte; Ana C. J. Costa; Waira S. Machida; Bruno F. Marques; Nicholas D. Mazzei; Poliana P. Menezes; Ludmila S. Resende; Juliana A. Shimoda; Renata S. Souza; André L. Acosta; et al. (Oecologia, 2026)
Bees are essential for ecosystem functioning, pollinating many wild and crop plant species. Predicting which species are most vulnerable to global changes, and how their loss may impact ecosystems and human well-being, is critical. Comprehensive information on bee response and effect traits is fundamental to these assessments. However, the Raunkiærian shortfall—insufficient trait data—remains significant for bees, particularly in the Neotropics. Moreover, it remains uncertain whether conservation strategies based on functional diversity from temperate regions can be generalized to the Neotropics. To address this gap, we compiled a comprehensive and validated dataset on Brazilian bee traits, covering 24 traits related to sociality (100% of the species with some information), nesting (88%), body size (71%), and buzzing capacity (42%) on 2,066 Brazilian bee species. The trait data here presented is a crucial resource for evaluating bee species' pollination effectiveness and susceptibility to global change. Comparative analysis with regions with ample trait data—USA, Europe, and China—revealed notable differences. Brazilian bees exhibited a higher prevalence of aboveground nesting species, especially compared to Europe. The proportion of eusocial species was also greater than in Europe and the United States, and more similar to China. Differently from other regions, Brazilian eusocial bees were significantly smaller than their non-eusocial counterparts. These cross-regional comparisons highlight the importance of geographically tailored conservation strategies and underscore the need for extensive trait data to accurately predict regional vulnerabilities and ecological impacts in a rapidly changing world.

Timing shapes flyway selection in juvenile white storks at the European migratory divide - Isabel Jorzik; Wolfgang Fiedler; Michael Kaatz; Shay Rotics; Ran Nathan; Martin Wikelski; Andrea Flack (Journal of Ornithology, 2026)
Migratory divides are junctures where populations of the same species following different migratory routes intersect. In white storks ( Ciconia ciconia ), migration strategies differ between the western and eastern flyways, yet the factors influencing flyway selection remain unclear. In this study, we used GPS tracking data from 151 juvenile storks to examine what determines flyway selection of juvenile, first-time migrants. Generalized linear mixed models revealed that timing-related variables were the primary factors correlated to flyway choice. Eastern flyway storks had significantly later fledging dates, shorter pre-migratory periods, and a narrower migration onset window compared to Western flyway storks. While temporal co-occurrence was observed in the overlap areas, western storks generally used these areas earlier. Wind and sex were not found to affect the juvenile flyway choice. Our results show that western storks may be experiencing favorable conditions of reduced time pressure and shorter overall migration routes. These migratory differences could still potentially contribute to the concurrent shift in population dynamics at the migratory divide toward the Western flyway, by inducing carry-over effects or affecting the adults' reproduction success. We suggest that understanding the dynamics of the migratory divide is important for maintaining behavioral diversity and preventing the loss of migratory routes.

Production and marketing of wine from the palm tree Hyphaene petersiana Klotzsch ex mart. (Arecaceae) in Banhine National Park, Mozambique - Isabel Uamba; Valdemiro Muhala; Angelina Martins; Cornélio Ntumi; Romari Alejandra Martinez; Alexandre Schiavetti (South African Journal of Botany, 2025)

Design, development and qualification of a european international berthing and docking mechanism (IBDM) - Joaquín Meléndez; Jeanette Bast; Johan Bogaerts; Jeremy Bouten; Angelo Costantino; Luc De Busser; Rutger De Nutte; Isabelle De Preter; Andy De Wilde; Felix De Wispelaere; Filip Dewitte; Wim Derkinderen; et al. (Journal of Space Safety Engineering, 2025)

Black spruce growth under climate extremes: Genetic insights for managing a key resource production species - Etienne Robert; Patrick Lenz; Yves Bergeron; Nathalie Isabel; Martin P. Girardin (Forest Ecology and Management, 2025)

Shear instabilities in Internal Solitary Waves under high and low-wind regimes - Jorge M. Magalhaes; Martin J. Coubard; José C.B. da Silva; Maarten C. Buijsman; Ana Isabel Santos; Ana Amorim; Paulo B. Oliveira (Continental Shelf Research, 2025)

3D-printed chitosan-starch mesh filled with minocycline-alginate hydrogel for dual anti-Staphylococcus aureus and osteogenic effects - Sara Cardoso; Victor Martin; Joana Cabrita Pereira; Ana Beatriz David; Rita Araújo; Lídia Gonçalves; Mariana Landin; Pedro Gomes; Maria Pia Ferraz; Isabel A.C. Ribeiro; Ana Bettencourt (Carbohydrate Polymers, 2025)

Leptospira licerasiae, a zoonotic pathogen isolated from water sources in Santa Maria, Rio Grande do Sul, Brazil - Patricia dos Santos Martins; Clarissa Luciano Barboza; Taynara Dias Lansarin; Sônia de Avila Botton; Ana Eucares von Laer; Camila Ezepha Coelho Leite; Walter Lilenbaum; Maria Isabel Nogueira Di Azevedo; Luis Antonio Sangioni (Brazilian Journal of Microbiology, 2025)

Conditional syndromes: Effect of human disturbance and age on the correlation between flight initiation distance and vigilance in marmots - Kenta Uchida; Isabel J. DeVito; Julien G.A. Martin; Daniel T. Blumstein (Behavioral Ecology and Sociobiology, 2025)
Behavioral syndromes—suites of correlated behaviors across different situations and contexts—are widespread and can have important ecological consequences because correlations between distinct behaviors shape how animals respond to changing environmental conditions and can limit behavioral plasticity. Behaviors such as vigilance, foraging, and exploration are correlated in many species and thus constitute a syndrome. Studying the structure of such syndromes is important to understand potential constraints on an animal’s behavioral response to the environment. Importantly, we know relatively little about antipredator behavioral syndromes and how their structure is associated with environmental conditions. Here, we estimated the correlation between two antipredator behaviors in yellow-bellied marmots ( Marmota flaviventer ): flight initiation distance (FID), which quantifies the flightiness of an animal in response to a potential predator and time allocation to vigilance while foraging, which represents an individual’s baseline level of wariness. We also examined the correlation between these traits under two different human disturbance levels by fitting a bivariate model on data collected over 18 years from 739 individuals. We found a modest positive among-individual correlation between FID and vigilance in adults, but no correlation between those variables in the much larger yearling cohort, nor when datasets for yearlings and adults were combined. We found no support for the hypothesis that human disturbance changed the structure of the syndrome (when present). Our study suggests that antipredator syndromes may be age-specific, and thus constraints on the independent expression of the behaviors underlying those are age-specific as well.

Worldwide Appraisal of Knowledge Gaps in the Space Usage of Small Pelagic Fish: Highlights Across Stock Uncertainties and Research Priorities - Ignacio A. Catalán; Noelle M. Bowlin; Matthew R. Baker; Florian Berg; Aaron Brazier; Timothée Brochier; Jana M. Del Favero; Susana Garrido; Douglas F. M. Gherardi; Stefanie Haase; Martin Huret; Matthias H. F. Kloppmann; et al. (Reviews in Fisheries Science & Aquaculture, 2025)

Towards circular textiles: Life cycle assessment of homewear produced from regenerative cotton and post-industrial waste versus conventional cotton - Teresa M. Mata; Inês Ruge; Hernâni Dias; Isabel Batista; Tércio Pinto; Ricardo Figueiredo; Alberto Figueiredo; António A. Martins (Journal of Cleaner Production, 2025)

Towards sustainable textile waste management: Exploring valuable chemicals production through steam cracking in a dual fluidized bed - Renesteban Forero-Franco; Isabel Cañete-Vela; Teresa Berdugo-Vilches; Chahat Mandviwala; Nidia Díaz Perez; Ivan Gogolev; Henrik Thunman; Martin Seemann (Fuel, 2025)

Protection and safety of aluminum hydroxide adjuvant and chimeric antigen containing predicted epitopes from bacteria murC gene in Aeromonas hydrophila fish infection - Jojo Silva Rodrigues; Maria Roméria da Silva; Camila Aparecida Martins; Laura Alves Zuanon; Karina Ventura Boechat Martins; Pedro Segantini Tótola; Jheneze Guimarães Pereira Rocha; Mariana Grôppo Parma; Isabel Samila Lima Castro; Tarciza Fernandes Nascimento; Allan Rodrigues Pires; Filipe Silveira Azevedo; et al. (Fish & Shellfish Immunology, 2025)

Polyphenol metabolism, short-chain fatty acids production, and microbiota changes during in vitro digestion and fermentation of Chilean beans (Phaseolus vulgaris L.) - Nélida Nina; Carlo Bressa; Beatriz de Lucas; Isabel Martin de la Torre; Felipe Jiménez-Aspee; Guillermo Schmeda-Hirschmann; Mar Larrosa (Food Chemistry, 2025)

Borealisation of Plant Communities in the Arctic Is Driven by Boreal‐Tundra Species - Mariana García Criado; Isabel C. Barrio; James D. M. Speed; Anne D. Bjorkman; Sarah C. Elmendorf; Isla H. Myers‐Smith; Rien Aerts; Juha M. Alatalo; Katlyn R. Betway‐May; Robert G. Björk; Mats P. Björkman; Daan Blok; et al. (Ecology Letters, 2025)
Following rapid climate change, tundra plant communities are experiencing extensive compositional shifts. A conservation concern is the potential encroachment of boreal species into the tundra (‘borealisation’). Tundra borealisation has been sporadically reported, but not systematically quantified. Here, we synthesised data from across 32 study areas, spanning 1137 plots and 287 vascular plant species, resurveyed between 1981 and 2023. We (i) quantified tundra borealisation as the colonisation and increase in abundance of Boreal and Boreal‐Tundra species, (ii) assessed biogeographical, climatic and local borealisation drivers and (iii) identified species contributing to borealisation and their associated traits. Half of the plots experienced borealisation, although borealisation rates were not different to random expectation. Borealisation was greater in Eurasia, closer to the treeline, at higher elevations, in warmer and wetter regions, where climate change was limited, and where initial boreal abundance was lower. Boreal coloniser species were generally short‐statured, and more often shrubs and graminoids. Boreal species colonised around three times less frequently than Boreal‐Tundra species. Hence, our findings indicate that tundra borealisation is mainly driven by the spread of already established boreal‐low Arctic tundra species. These plant community composition changes could have cascading impacts on land‐atmosphere interactions, trophic dynamics and Indigenous and local livelihoods.

Evaluation of climate, water and peloid of the Pink Lagoon of Torrevieja and its possible use in thalassotherapy - Francisco Maraver; Jose M. Carbajo; Francisco Armijo; Lourdes Aguilera; Ana Isabel Martin-Megias; Miguel Angel Fernandez-Toran; María Virginia Fernandez-Gonzalez; María Lorena Vela (International Journal of Biometeorology, 2025)

The impact of biochar application on sponge function, water erosion, and vegetation cover in a Mediterranean vineyard soil - Behrouz Gholamahmadi; Oscar Gonzalez Pelayo; Suyan Isaka; Isabel Campos; Martinho Martins; Ana Catarina Bastos; Marjan Jongen; Frank G.A. Verheijen (Journal of Environmental Management, 2025)

The impact of endocrine disrupting chemicals on adrenal corticosteroids – A systematic review of epidemiological studies - Isabel Stüfchen; Júnia R.O.L. Schweizer; Friederike Völter; Elisabeth Nowak; Leah Braun; Julien Kocabiyik; Michael Mederos y Schnitzler; Tracy Ann Williams; Sonja Kunz; Martin Bidlingmaier; Martin Reincke (Environmental Research, 2025)

Cortical volumetry and longitudinal cognitive changes in Parkinson’s disease: insights from the COPPADIS cohort - Tania Álvarez-Avellón; Carmen Solares; Juan Álvarez-Carriles; Pablo Franco-Rosado; Patricia Diaz-Galvan; Diego Santos-García; Pablo Mir; Manuel Menéndez-González; Astrid Adarmes Daniela; Almeria Marta; Maria Gema Alonso Losada; Araceli Alonso Cánovas; et al. (Brain Imaging and Behavior, 2025)
Cognitive decline is a major non-motor symptom in Parkinson’s disease (PD), often linked to brain atrophy. This study examines the relationship between cortical atrophy and age groups in predicting cognitive decline in PD over five years. 188 PD patients from the COPPADIS cohort were stratified by age: young (30–55 years, N = 47), middle-aged (56–65 years, N = 59), and older adults (66–75 years, N = 82). Baseline cortical volume was assessed using T1-weighted MRI, and cognitive decline was evaluated using the annual rate of change of the Parkinson’s Disease-Cognitive Rating Scale (PD-CRS). Parametric or non-parametric tests were applied to evaluate group differences. Main analyses consist of several multiple regression analyses to examine associations between baseline brain atrophy and cognitive decline by age group. Older adults exhibited significantly greater cognitive decline in comparison to the younger age groups in the three compose scores of the PDCRS -Fronto-subcortical (H(2) = 41.08, p < 0.001), Posterior Cortical (H(2) = 22.03, p < 0.001), and Total(H(2) = 41.13, p < 0.001). Higher educational level has a significant positive effect on older adults, specifically for working memory performance, delayed verbal memory and the fronto-subcortical composed score. Multiple regression models underscored the predictive value of the bilateral hippocampus, bilateral medial orbitofrontal cortex, right precuneus, and right isthmus cingulate gyrus, together with being an older adult or having a higher education. MRI measures, age, and education predict cognitive decline in PD. Longitudinal assessments are essential for refining atrophy-cognition correlations and optimizing patient stratification.

A global assessment of microplastic abundance and characteristics on marine turtle nesting beaches - Zara L.R. Botterell; Jed Ardren; Elly Dove; Ellen McArthur; David S. Addison; Oyeronke M. Adegbile; Pierre Didier Agamboue; Andrews Agyekumhene; Phil Allman; Alexandra Alterman; Adren Anderson; Theresa Arenholz; et al. (Marine Pollution Bulletin, 2025)

Influence of extenders and antioxidants on Nile tilapia (Oreochromis niloticus) sperm parameters - Vinícius Wagner Silva; Myrian Megumy Tsunokawa Hidalgo; Renan José Casarotto Appel; Karine Nicole Siqueira; José Beirão; Laurival Antônio Vilas-Boas; Lucienne Garcia Pretto-Giordano; Rajesh Joshi; Jorge Manuel de Oliveira Fernandes; Maria Isabel Mello Martins (Cryobiology, 2025)

Effects of solid-state fermentation of Gelidium corneum by-product on immune status and gut microbiota in European seabass - Marta Ferreira; Catarina Ramos-Oliveira; Rui Magalhães; Nicole Martins; Cláudia R. Serra; José Manuel Salgado; Isabel Belo; A. Oliva-Teles; Helena Peres (Animal Feed Science and Technology, 2025)

Fossil leaf cuticle: Best practices for preparation and paleo-CO2 analysis - Xiaoqing Zhang; Dana L. Royer; Carina E. Colombi; Juan Martin Drovandi; Jennifer C. McElwain; Gaëtan Guignard; Qin Leng; Barry H. Lomax; Nathan D. Sheldon; Rebekah A. Stein; Garland R. Upchurch; Yongdong Wang; et al. (Earth-Science Reviews, 2025)

ms2: A molecular simulation tool for thermodynamic properties, release 5.0 - Isabel Nitzke; Gabriela Guevara-Carrion; Denis Saric; Simon Homes; Simon Stephan; Robin Fingerhut; Martin Bernreuther; Hans Hasse; Jadran Vrabec (Computer Physics Communications, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Acoustic wave propagation in oil wells: A comparison between semi-analytical and finite element modeling approaches - Luis Paulo Brasil de Souza; Juan Andrés Santisteban Hidalgo; Tiago de Magalhães Correia; Isabel Giron Camerini; Guilherme Rezende Bessa Ferreira; Antônio de Souza Rodrigues; Alan Conci Kubrusly; Arthur Martins Barbosa Braga (Wave Motion, 2025)

Induction of systemic defense responses in tomato against Clavibacter michiganensis by application of aerated compost tea - Víctor Adrián Hernández-Aranda; Martin Escoto-Rodríguez; Gisela Aguilar-Benítez; Ramón Jarquin-Gálvez; Juan Manuel Cevallos-Cevallos; Patricia Isabel Manzano-Santana; Iván Andrés Chóez-Guaranda; José Pablo Lara-Ávila (European Journal of Plant Pathology, 2025)

Anti-Pythium insidiosum activity of three novel triazole compounds: synthesis, pharmacokinetic and toxicological parameters - Carolina Martins Fernandes; Alessandro de Souza Prestes; Lara Baccarin Ianiski; Aline Fontanella Maciel; Bruna Godoy Noro; Fernanda D’Avila da Silva; Bruno Stefanello Vizzotto; Sônia de Avila Botton; Ricardo Frederico Schumacher; Daniela Isabel Brayer Pereira; Nilda Vargas Barbosa (Brazilian Journal of Microbiology, 2025)

Essential and nonessential fatty acid composition and use in overwintering monarch butterflies - Libesha Anparasan; Matthias Pilecky; M. Isabel Ramirez; Keith A. Hobson; Martin J. Kainz; Leonard I. Wassenaar (Journal of Comparative Physiology A, 2025)

Secondary metabolites of cyanobacteria from Cape Verde Archipelago act as NO donors with potential application in dermatology and cosmetics - Janaína Morone; Guilherme Scotta Hentschke; Isabel Benta Oliveira; Vitor Vasconcelos; Rosário Martins; Graciliana Lopes (Algal Research, 2025)

Beta-carotene-loaded Oleogels: Morphological analysis, cytotoxicity assessment, in vitro digestion and intestinal permeability - Artur J. Martins; Lara Perdigão; Catarina Gonçalves; Isabel R. Amado; Cristiano S. Abreu; António A. Vicente; Rosiane L. Cunha; Lorenzo M. Pastrana; Miguel A. Cerqueira (Food Chemistry, 2025)

Globale Ziele, lokale Stimmen: Jugend führt multilaterale Dialoge - Esteban Charria-Girón; Stefan Sorge; Adriana Martin; Sergio Bolívar; María Isabel Gutiérrez; Natalia Matiz-Rubio (BIOspektrum, 2025)

Evaluation of the potential of annatto seed powder to reduce the formation of heterocyclic amines in charcoal-grilled and pan-fried beef patties - Thaís de Moura Neves-Gonçalves; Edgar Pinto; Olga Viegas; Anna Rafaela Cavalcante Braga; Leonardo M. de Souza Mesquita; Isabel Maria Pinto Leite Viegas Oliveira Ferreira; Carmen García-Jares; Veridiana Vera De Rosso; Semíramis Martins Álvares Domene (Food Chemistry, 2025)

Cryopreservation influence on DNA methylation profile in Nile tilapia (Oreochromis niloticus) spermatozoa - Myrian Megumy Tsunokawa Hidalgo; Douglas Martins Cecconello; Renan Casarotto Appel; Vinicius Wagner Silva; Lorena Maria Rudnik; Partha Sarathi Tripathy; Laurival Antônio Vilas-Boas; Lucienne Garcia Pretto Giordano; Jorge Manuel de Oliveira Fernandes; Maria Isabel Mello Martins (Animal Reproduction Science, 2025)

Addition of antioxidant uric acid in extender for Nile tilapia (Oreochromis niloticus) sperm cryopreservation - Vinicius Wagner Silva; Myrian Megumy Tsunokawa Hidalgo; Renan Casarotto Appel; Karine Nicole Siqueira; Laurival Antônio Vilas-Boas; Luciene Garcia Pretto Giordano; Jorge Manuel de Oliveira Fernandes; José Beirão dos Santos; Maria Isabel Mello Martins (Animal Reproduction Science, 2025)

Correlation between ultrasound evaluation of the prostate and age, weight, kinetics and sperm morphology of German Spitz breeders - Bruno Alcantara Buzato; Luiz Guilherme Corsi Trautwein; Myrian Megumy Tsunokawa Hidalgo; Leticia Amanda dos Santos Silva; Julia Rodrigues Greghi; Vinicius Wagner Silva; Natalia Ribeiro Sambatti; Maria Isabel Mello Martins (Animal Reproduction Science, 2025)

Revisiting the cytogenetics of Vellozia Vand.: immunolocalization of KNL1 elucidates the chromosome number for the genus - Guilherme T. Braz; Lucas B. Riboldi; Maísa S. Pinto; Eliana R. Forni-Martins; Juliana E. C. T. Yassitepe; Ricardo A. Dante; Isabel R. Gerhardt (Brazilian Journal of Botany, 2024)
Chromosome number is the most fundamental trait of a karyotype. Accurate chromosome counting is essential for further analyses including cytogenomics, taxonomic, evolutionary, and genomic studies. Despite its importance, miscounting is common, especially in early publications on species with small and morphologically similar chromosomes. Vellozia Vand. is a genus mainly distributed throughout South America belonging to the angiosperm family Velloziaceae, a dominant taxon in the Brazilian “campos rupestres”. Cytogenetic studies within the group have been rare and have shown conflicting chromosome counts, even within the same species. These discrepancies are associated with the presence of a few small chromosome-like structures, which were previously classified as possible satellites. Here, to accurately determine the chromosome number of species belonging to the genus, we used different cytogenomics approaches, including the immunostaining of the KNL1 kinetochore protein combined with chromosome spread preparation using tissue culture-derived samples. Our results revealed 2 n = 18 chromosomes for all six species studied. This finding suggests that the basic chromosome number for Vellozia is x = 9 and not x = 8, as previously proposed. The immunolocalization of functional centromeres was fundamental for undoubtedly identifying the smaller chromosome pair as real chromosomes and accurately determining the correct chromosome number of these species. This will provide substantial support for further studies, including investigations into karyotype evolution and the generation of reference genomes for the species of the family.

Requiem for Argentine mammals: A spatial framework for mapping extinction risk - Gabriel M. Martin; Baltazar González; Federico Brook; Melina Zuliani; Agustín M. Abba; Sebastián Cirignoli; Soledad de Bustos; M.Mónica Díaz; Isabel Gómez Villafañe; Martín Kowalewski; Matías S. Mora; Agustina Ojeda; et al. (Journal for Nature Conservation, 2024)

Bacterial cellulose nanocrystals or nanofibrils as Pickering stabilizers in low-oil emulsions: A comparative study - Náyra O.F. Pinto; Ana Isabel Bourbon; Daniela Martins; André Pereira; Miguel A. Cerqueira; Lorenzo Pastrana; Miguel Gama; Henriette M.C. Azeredo; Morsyleide F. Rosa; Catarina Gonçalves (Food Hydrocolloids, 2024)

Cardiac embryonal rhabdomyosarcoma in a domestic shorthair cat - Anahi Souza Silva; Isabela Leite Doretto; Isabel Luana de Macêdo; Liz de Albuquerque Cerqueira; Christine Souza Martins; Cristiano Barros de Melo; Márcio Botelho de Castro (Topics in Companion Animal Medicine, 2024)

Influence of polystyrene nanoplastics on the toxicity of haloperidol to amphibians: An in vivo and in vitro approach - Filipa Morais; Valérie Pires; Mónica Almeida; Manuel A. Martins; Miguel Oliveira; Isabel Lopes (Science of The Total Environment, 2024)

Nano-hydroxyapatite Pickering emulsions as edible mayonnaise-like food sauce templates: A novel approach for food design - Maria Eduarda Relvas; Larissa C. Ghirro; Isabel M. Martins; Jose Carlos B. Lopes; Madalena M. Dias; Maria Filomena Barreiro; Andreia Ribeiro (Journal of Food Engineering, 2024)

Insights into the development of carbon molecular sieve membranes from polymer blends for gas separation: A review - Thaís Martins Neves; Liliane Damaris Pollo; Nilson Romeu Marcilio; Isabel Cristina Tessaro (Gas Science and Engineering, 2024)

Steam cracking in a semi-industrial dual fluidized bed reactor: Tackling the challenges in thermochemical recycling of plastic waste - Chahat Mandviwala; Renesteban Forero Franco; Teresa Berdugo Vilches; Ivan Gogolev; Judith González-Arias; Isabel Cañete Vela; Henrik Thunman; Martin Seemann (Chemical Engineering Journal, 2024)

Fruitbody and root data infer different environmental niches for ectomycorrhizal fungi - Muyao Qi; Laura M. Suz; Martin I. Bidartondo; C. David L. Orme; Guillaume Delhaye; Isabel Openshaw; Carolina Tovar (Journal of Biogeography, 2024)
Aim We used two fungal data sources for occurrence records (fruitbodies and roots) to (1) test the influence of data source on estimating the environmental niche of ectomycorrhizal (ECM) fungi and (2) compare the differences in estimated niche area and density for ECM fungal species with conspicuous (easily observed, i.e. mushrooms) versus inconspicuous (difficult to observe and/or usually overlooked, i.e. crusts and truffles) fruitbodies. Location Europe. Taxon Sixty‐six ectomycorrhizal fungi. Methods We used fungal records obtained from fruitbody and root data of 66 common ECM fungal species in European forests to estimate their environmental niches. The fruitbody data were extracted from public databases (GBIF, UNITE), while the root data (from individual ectomycorrhizas) were obtained from a dataset of 136 ICP Forests long‐term intensive monitoring plots. We estimated the niches for combined data sources (fruitbody and root data) and for each individual data source using six key environmental variables for ECM fungal community composition. We then examined how estimated niche overlap and area (number of cells in niche grid) varied for the two data sources between conspicuous and inconspicuous species. Results We found that although the niches estimated using combined data from the two data sources had high overlap with the niches estimated from fruitbody data, the niches estimated from fruitbody data had low or medium overlap with the niches estimated using root data for most ECM fungi. The overlap between the two data sources for conspicuous species was significantly larger than that for inconspicuous species. Root data were important for estimating the niche of inconspicuous species, which had a high ratio of root data to fruitbody data. Main Conclusion Our results indicate that although fruitbody data suffice for estimating the environmental niche for most conspicuous ECM fungi, combined datasets including fruitbody and root data can improve the accuracy of estimated niches and should be used. Root data for inconspicuous species are particularly useful, and thus, adopting root data in niche estimation will better infer the niches of ECM fungi. Inferring niches along environmental variables can guide future sampling and conservation of fungi.

No Future Growth Enhancement Expected at the Northern Edge for European Beech due to Continued Water Limitation - Stefan Klesse; Richard L. Peters; Raquel Alfaro‐Sánchez; Vincent Badeau; Claudia Baittinger; Giovanna Battipaglia; Didier Bert; Franco Biondi; Michal Bosela; Marius Budeanu; Vojtěch Čada; J. Julio Camarero; et al. (Global Change Biology, 2024)
With ongoing global warming, increasing water deficits promote physiological stress on forest ecosystems with negative impacts on tree growth, vitality, and survival. How individual tree species will react to increased drought stress is therefore a key research question to address for carbon accounting and the development of climate change mitigation strategies. Recent tree‐ring studies have shown that trees at higher latitudes will benefit from warmer temperatures, yet this is likely highly species‐dependent and less well‐known for more temperate tree species. Using a unique pan‐European tree‐ring network of 26,430 European beech ( Fagus sylvatica L. ) trees from 2118 sites, we applied a linear mixed‐effects modeling framework to (i) explain variation in climate‐dependent growth and (ii) project growth for the near future (2021–2050) across the entire distribution of beech. We modeled the spatial pattern of radial growth responses to annually varying climate as a function of mean climate conditions (mean annual temperature, mean annual climatic water balance, and continentality). Over the calibration period (1952–2011), the model yielded high regional explanatory power ( R 2 = 0.38–0.72). Considering a moderate climate change scenario (CMIP6 SSP2‐4.5), beech growth is projected to decrease in the future across most of its distribution range. In particular, projected growth decreases by 12%–18% (interquartile range) in northwestern Central Europe and by 11%–21% in the Mediterranean region. In contrast, climate‐driven growth increases are limited to around 13% of the current occurrence, where the historical mean annual temperature was below ~6°C. More specifically, the model predicts a 3%–24% growth increase in the high‐elevation clusters of the Alps and Carpathian Arc. Notably, we find little potential for future growth increases (−10 to +2%) at the poleward leading edge in southern Scandinavia. Because in this region beech growth is found to be primarily water‐limited, a northward shift in its distributional range will be constrained by water availability.

Fermented agar by-product and sunflower cake mixture as feedstuff for European seabass (Dicentrarchus labrax) - Marta Ferreira; Catarina Ramos-Oliveira; Rui Magalhães; Nicole Martins; Rodrigo O.A. Ozório; José Manuel Salgado; Isabel Belo; Aires Oliva-Teles; Helena Peres (Animal Feed Science and Technology, 2024)

Proximal microclimate: Moving beyond spatiotemporal resolution improves ecological predictions - David H. Klinges; J. Alex Baecher; Jonas J. Lembrechts; Ilya M. D. Maclean; Jonathan Lenoir; Caroline Greiser; Michael Ashcroft; Luke J. Evans; Michael R. Kearney; Juha Aalto; Isabel C. Barrio; Pieter De Frenne; et al. (Global Ecology and Biogeography, 2024)
Aim The scale of environmental data is often defined by their extent (spatial area, temporal duration) and resolution (grain size, temporal interval). Although describing climate data scale via these terms is appropriate for most meteorological applications, for ecology and biogeography, climate data of the same spatiotemporal resolution and extent may differ in their relevance to an organism. Here, we propose that climate proximity, or how well climate data represent the actual conditions that an organism is exposed to, is more important for ecological realism than the spatiotemporal resolution of the climate data. Location Temperature comparison in nine countries across four continents; ecological case studies in Alberta (Canada), Sabah (Malaysia) and North Carolina/Tennessee (USA). Time Period 1960–2018. Major Taxa Studied Case studies with flies, mosquitoes and salamanders, but concepts relevant to all life on earth. Methods We compare the accuracy of two macroclimate data sources (ERA5 and WorldClim) and a novel microclimate model ( microclimf ) in predicting soil temperatures. We then use ERA5, WorldClim and microclimf to drive ecological models in three case studies: temporal (fly phenology), spatial (mosquito thermal suitability) and spatiotemporal (salamander range shifts) ecological responses. Results For predicting soil temperatures, microclimf had 24.9% and 16.4% lower absolute bias than ERA5 and WorldClim respectively. Across the case studies, we find that increasing proximity (from macroclimate to microclimate) yields a 247% improvement in performance of ecological models on average, compared to 18% and 9% improvements from increasing spatial resolution 20‐fold, and temporal resolution 30‐fold respectively. Main Conclusions We propose that increasing climate proximity, even if at the sacrifice of finer climate spatiotemporal resolution, may improve ecological predictions. We emphasize biophysically informed approaches, rather than generic formulations, when quantifying ecoclimatic relationships. Redefining the scale of climate through the lens of the organism itself helps reveal mechanisms underlying how climate shapes ecological systems.

Identifying drivers of non-stationary climate-growth relationships of European beech - Christopher Leifsson; Allan Buras; Stefan Klesse; Claudia Baittinger; Banzragch Bat-Enerel; Giovanna Battipaglia; Franco Biondi; Branko Stajić; Marius Budeanu; Vojtěch Čada; Liam Cavin; Hugues Claessens; et al. (Science of The Total Environment, 2024)

Concanavalin A, lectin from Canavalia ensiformis seeds has Leishmania infantum antipromastigote activity mediated by carbohydrate recognition domain - Ana Lúcia Estevam dos Santos; Racquel Oliveira Silva Souza; Flávia Eduarda Vidal Barbosa; Maria Helena Cruz dos Santos; Yasmim Alencar Grangeiro; Alice Maria Costa Martins; Gabriela Santos-Gomes; Isabel Pereira da Fonseca; Cláudio Gleidiston Lima da Silva; Claudener Souza Teixeira (Chemico-Biological Interactions, 2024)

The impact and future of artificial intelligence in medical genetics and molecular medicine: an ongoing revolution - Firat Ozcelik; Mehmet Sait Dundar; A. Baki Yildirim; Gary Henehan; Oscar Vicente; José A. Sánchez-Alcázar; Nuriye Gokce; Duygu T. Yildirim; Nurdeniz Nalbant Bingol; Dijana Plaseska Karanfilska; Matteo Bertelli; Lejla Pojskic; et al. (Functional & Integrative Genomics, 2024)

Evaluation of the testicular artery Doppler velocimetry and its correlation with sperm defects in domestic cats - Luiz Guilherme Corsi Trautwein; Myrian Megumy Tsunokawa Hidalgo; Ana Beatriz Marques de Almeida; Jamile Haddad Neta; Guilherme Schiess Cardoso; Karina Keller Marques da Costa Flaiban; Vinícius Wagner Silva; Leticia Amanda dos Santos Silva; Maria Isabel Mello Martins (Animal Reproduction Science, 2024)

Responsible ownership and health education can reduce the time of sporotrichosis treatment in domestic cats - Bianca Moreira de Souza; Salene Angelini Colombo; Roberta do Carmo Teixeira; Isadora Martins Pinto Coelho; Werik dos Santos Barrado; Breno Oliveira Lima Ramos; Érica Lorenza Martins Araujo; Gustavo Canesso Bicalho; Maria Isabel de Azevedo; Kelly Moura Keller; Fabiana Dos Santos Monti; Lorena Diniz Macedo Silva Maia; et al. (Preventive Veterinary Medicine, 2024)

Rhododendron poisoning in alpacas (Vicugna pacos) in Northern Germany - Johannes Schregel; Isabel Zdora; Ingo Gerhauser; Teresa Maria Punsmann; Sabine Aboling; Martin Ganter; Matthias Gerhard Wagener (Veterinary Research Communications, 2024)
Poisoning is often suspected to be the origin of disease in South American camelids (SACs) by owners, but only in a few cases this assumption can be confirmed. In small ruminants, rhododendron poisoning is a common emergency for livestock veterinarians. However, this condition has rarely been reported in SACs so far. This paper provides information regarding clinical findings, hematology, clinical chemistry, and treatment of four alpacas after presumed intake of rhododendron leaves including pathological findings of one of the animals. Rhododendron leaves contain grayanatoxins that lead to hyperpolarization of excitable cells. Clinical signs that were observed in the presented alpacas comprised: salivation, dehydration, decreased motility of compartment 1, uncoordinated regurgitation, and cardiac arrhythmia. Clinical chemistry revealed that rhododendron poisoning was associated with metabolic acidosis and azotaemia, hyponatremia and hyperkalemia. Most striking macroscopic and histopathological findings included gastric ulceration, and renal infarcts along with inflammatory changes. Leaves of Rhododendron spp. were identified in the forestomach content of this animal. Affected animals were treated symptomatically as there is no specific antidote in rhododendron poisoning. This included parenteral rehydration, treatment of metabolic acidosis (infusion of sodium bicarbonate solution), and oral administration of activated charcoal to bind potential toxins. In addition, antibiotic treatment might be necessary to prevent aspiration pneumonia in case of uncoordinated regurgitation. Of the four animals, the worst affected alpaca was euthanized, one had minimal signs and two responded to supportive care and recovered. In conclusion, rhododendron poisoning might be fatal for alpacas in individual cases and therefore rhododendron bushes should not be placed in the habitat of SACs.

Oak genomics for nature-based solutions: shaping future forests and resilient landscapes in Canada - Lisa Tischenko; Martin Williams; Ian DeMerchant; Kishan Sambaraju; Melanie Zacharias; Raju Soolanayakanahally; Guillaume Otis-Prudhomme; Nathalie Isabel; Ilga Porth (Tree Genetics & Genomes, 2024)

Cultivable Root-Symbiotic Bacteria of a Pioneer Ericaceous Dwarf Shrub Colonizing Volcanic Deposits and Their Potential to Promote host Fitness - Alejandra Fuentes-Quiroz; Héctor Herrera; Roxana Alvarado; Cristiane Sagredo-Saez; Maria Isabel-Mujica; Martin Vohník; Eleonora Rolli (Journal of Soil Science and Plant Nutrition, 2024)

Future carbon sequestration potential in a widespread transcontinental boreal tree species: Standing genetic variation matters! - Etienne Robert; Patrick Lenz; Yves Bergeron; Guillaume de Lafontaine; Olivier Bouriaud; Nathalie Isabel; Martin P. Girardin (Global Change Biology, 2024)
Climate change (CC) necessitates reforestation/afforestation programs to mitigate its impacts and maximize carbon sequestration. But comprehending how tree growth, a proxy for fitness and resilience, responds to CC is critical to maximize these programs' effectiveness. Variability in tree response to CC across populations can notably be influenced by the standing genetic variation encompassing both neutral and adaptive genetic diversity. Here, a framework is proposed to assess tree growth potential at the population scale while accounting for standing genetic variation. We applied this framework to black spruce (BS, Picea mariana [Mill] B.S.P.), with the objectives to (1) determine the key climate variables having impacted BS growth response from 1974 to 2019, (2) examine the relative roles of local adaptation and the phylogeographic structure in this response, and (3) project BS growth under two Shared Socioeconomic Pathways while taking standing genetic variation into account. We modeled growth using a machine learning algorithm trained with dendroecological and genetic data obtained from over 2600 trees (62 populations divided in three genetic clusters) in four 48‐year‐old common gardens, and simulated growth until year 2100 at the common garden locations. Our study revealed that high summer and autumn temperatures negatively impacted BS growth. As a consequence of warming, this species is projected to experience a decline in growth by the end of the century, suggesting maladaptation to anticipated CC and a potential threat to its carbon sequestration capacity. This being said, we observed a clear difference in response to CC within and among genetic clusters, with the western cluster being more impacted than the central and eastern clusters. Our results show that intraspecific genetic variation, notably associated with the phylogeographic structure, must be considered when estimating the response of widespread species to CC.

Internalization and toxicity of polystyrene nanoplastics on inmortalized human neural stem cells - Ma Carmen González-Caballero; Mercedes de Alba González; Mónica Torres-Ruiz; Patricia Iglesias-Hernández; Verónica Zapata; María C. Terrón; Martin Sachse; Mónica Morales; Raquel Martin-Folgar; Isabel Liste; Ana I. Cañas-Portilla (Chemosphere, 2024)

Contrasting physiological strategies explain heterogeneous responses to severe drought conditions within local populations of a widespread conifer - Claire Depardieu; Patrick Lenz; Joelle Marion; Simon Nadeau; Martin P. Girardin; William Marchand; Christian Bégin; Kerstin Treydte; Arthur Gessler; Jean Bousquet; Martine M. Savard; Nathalie Isabel (Science of The Total Environment, 2024)

A novel mouse model for familial hypocalciuric hypercalcemia (FHH1) reveals PTH-dependent and independent CaSR defects - Catharina J. Küng; Arezoo Daryadel; Rocio Fuente; Betül Haykir; Martin Hrabĕ de Angelis; Nati Hernando; Isabel Rubio-Aliaga; Carsten A. Wagner (Pflügers Archiv - European Journal of Physiology, 2024)
The Calcium-sensing receptor (CaSR) senses extracellular calcium, regulates parathyroid hormone (PTH) secretion, and has additional functions in various organs related to systemic and local calcium and mineral homeostasis. Familial hypocalciuric hypercalcemia type I (FHH1) is caused by heterozygous loss-of-function mutations in the CaSR gene, and is characterized by the combination of hypercalcemia, hypocalciuria, normal to elevated PTH, and facultatively hypermagnesemia and mild bone mineralization defects. To date, only heterozygous Casr null mice have been available as model for FHH1. Here we present a novel mouse FHH1 model identified in a large ENU-screen that carries an c.2579 T > A (p.Ile859Asn) variant in the Casr gene ( Casr BCH002 mice). In order to dissect direct effects of the genetic variant from PTH-dependent effects, we crossed Casr BCH002 mice with PTH deficient mice. Heterozygous Casr BCH002 mice were fertile, had normal growth and body weight, were hypercalcemic and hypermagnesemic with inappropriately normal PTH levels and urinary calcium excretion replicating some features of FHH1. Hypercalcemia and hypermagnesemia were independent from PTH and correlated with higher expression of claudin 16 and 19 in kidneys. Likewise, reduced expression of the renal TRPM6 channel in Casr BCH002 mice was not dependent on PTH. In bone, mutations in Casr rescued the bone phenotype observed in Pth null mice by increasing osteoclast numbers and improving the columnar pattern of chondrocytes in the growth zone. In summary, Casr BCH002 mice represent a new model to study FHH1 and our results indicate that only a part of the phenotype is driven by PTH.

Reading tea leaves worldwide: Decoupled drivers of initial litter decomposition mass‐loss rate and stabilization - Judith M. Sarneel; Mariet M. Hefting; Taru Sandén; Johan van den Hoogen; Devin Routh; Bhupendra S. Adhikari; Juha M. Alatalo; Alla Aleksanyan; Inge H. J. Althuizen; Mohammed H. S. A. Alsafran; Jeff W. Atkins; Laurent Augusto; et al. (Ecology Letters, 2024)
The breakdown of plant material fuels soil functioning and biodiversity. Currently, process understanding of global decomposition patterns and the drivers of such patterns are hampered by the lack of coherent large‐scale datasets. We buried 36,000 individual litterbags (tea bags) worldwide and found an overall negative correlation between initial mass‐loss rates and stabilization factors of plant‐derived carbon, using the Tea Bag Index (TBI). The stabilization factor quantifies the degree to which easy‐to‐degrade components accumulate during early‐stage decomposition (e.g. by environmental limitations). However, agriculture and an interaction between moisture and temperature led to a decoupling between initial mass‐loss rates and stabilization, notably in colder locations. Using TBI improved mass‐loss estimates of natural litter compared to models that ignored stabilization. Ignoring the transformation of dead plant material to more recalcitrant substances during early‐stage decomposition, and the environmental control of this transformation, could overestimate carbon losses during early decomposition in carbon cycle models.

Camera trap surveys of A tlantic F orest mammals: A data set for analyses considering imperfect detection (2004–2020) - Ingridi Camboim Franceschi; Rubem Augusto da Paixão Dornas; Isabel Salgueiro Lermen; Artur Vicente Pfeifer Coelho; Ademir Henrique Vilas Boas; Adriano Garcia Chiarello; Adriano Pereira Paglia; Agnis Cristiane de Souza; Alana Rafaela Borsekowsky; Alessandro Rocha; Alex Bager; Alexander Zaidan de Souza; et al. (Ecology, 2024)
Camera traps became the main observational method of a myriad of species over large areas. Data sets from camera traps can be used to describe the patterns and monitor the occupancy, abundance, and richness of wildlife, essential information for conservation in times of rapid climate and land‐cover changes. Habitat loss and poaching are responsible for historical population losses of mammals in the Atlantic Forest biodiversity hotspot, especially for medium to large‐sized species. Here we present a data set from camera trap surveys of medium to large‐sized native mammals (>1 kg) across the Atlantic Forest. We compiled data from 5380 ground‐level camera trap deployments in 3046 locations, from 2004 to 2020, resulting in 43,068 records of 58 species. These data add to existing data sets of mammals in the Atlantic Forest by including dates of camera operation needed for analyses dealing with imperfect detection. We also included, when available, information on important predictors of detection, namely the camera brand and model, use of bait, and obstruction of camera viewshed that can be measured from example pictures at each camera location. Besides its application in studies on the patterns and mechanisms behind occupancy, relative abundance, richness, and detection, the data set presented here can be used to study species' daily activity patterns, activity levels, and spatiotemporal interactions between species. Moreover, data can be used combined with other data sources in the multiple and expanding uses of integrated population modeling. An R script is available to view summaries of the data set. We expect that this data set will be used to advance the knowledge of mammal assemblages and to inform evidence‐based solutions for the conservation of the Atlantic Forest. The data are not copyright restricted; please cite this paper when using the data.

Extraction of macroalgae phenolic compounds for cosmetic application using eutectic solvents - João M. Santos; Bárbara C. Jesus; Helena Ribeiro; Alice Martins; Joana Marto; Manuel Fitas; Pedro Pinto; Celso Alves; Joana Silva; Rui Pedrosa; Isabel M. Marrucho (Algal Research, 2024)

Evaluation of the Anti-biofilm Efficacy of Kyotorphin Derivatives and Biosafety Assessment: In Vitro and In Vivo Investigations Targeting Bacterial and Fungal Pathogens - Isabel Chaves Silva Carvalho; Fernanda da Silva Seiffert Simões; Vitor Martins de Andrade; Dayane Batista Tada; Montserrat Heras; Eduard Bardají; Mônica Lopes Ferreira; Miguel Augusto Rico Botas Castanho; Katia Conceição (International Journal of Peptide Research and Therapeutics, 2024)

Triclosan and its alternatives, especially chlorhexidine, modulate macrophage immune response with distinct modes of action - Stefanie Raps; Laura Bahr; Isabel Karkossa; Manuela Rossol; Martin von Bergen; Kristin Schubert (Science of The Total Environment, 2024)

Amazon deforestation: A dangerous future indicated by patterns and trajectories in a hotspot of forest destruction in Brazil - Beatriz Figueiredo Cabral; Aurora Miho Yanai; Paulo Maurício Lima de Alencastro Graça; Maria Isabel Sobral Escada; Cláudia Maria de Almeida; Philip Martin Fearnside (Journal of Environmental Management, 2024)

Living benthic foraminifera from Almirante Câmara and Grussaí canyons and adjacent slope areas (Campos Basin, Southwest Atlantic): Response to trophic and hydrodynamic conditions - Silvia Helena Mello Sousa; Cintia Yamashita; Thaisa Marques Vicente; Rafaela Nogueira Mendonça Mendes; Laetitia Licari; Maria Virgínia Alves Martins; Bianca Sung Mi Kim; Christian Millo; Renato Carreira; Isabel Montoya-Montes; Michael A. Kaminski; Michel Michaelovitch Mahiques (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Feedstock recycling of cable plastic residue via steam cracking on an industrial-scale fluidized bed - Isabel Cañete Vela; Jelena Maric; Judith González-Arias; Martin Seemann (Fuel, 2024)

Haplotype diversity patterns in Quercus suber (Fagaceae) inferred from cpDNA sequence data - Filipe Sousa; Mariana Bray Viegas; Joana Costa; Isabel Marques; Francisco Pina-Martins; Fernanda Simões; José Matos; Maria Glushkova; Célia Miguel; Maria Manuela Veloso; M. Margarida Oliveira; Cândido Pinto Ricardo; et al. (Plant Systematics and Evolution, 2023)
Chloroplast genome diversity in cork oak ( Quercus suber ) is characterised by the occurrence of haplotypes that are akin to those found in other Mediterranean oak species, particularly in Q. ilex and Q. rotundifolia , suggesting the possible presence of an introgressed chloroplast lineage. To further investigate this pattern, we reconstructed chloroplast haplotypes by sequencing four chloroplast markers (cpDNA), sampled across 181 individuals and 10 taxa. Our analyses resulted in the identification of two diversified chloroplast haplogroups in Q. suber , corresponding to a geographically widespread lineage and an Afro-Iberian lineage. Time-calibrated phylogenetic analyses of cpDNA point to a Miocene origin of the two haplogroups in Q. suber , suggesting that the Afro-Iberian lineage was present in cork oak before the onset of glaciation periods. The persistence of the two haplogroups in the western part of the species distribution range may be a consequence of either ancient introgression events or chloroplast lineage sorting, combined with different fixation in refugia through glaciation periods. Our results provide a comprehensive insight on the origins of chloroplast diversity in these ecologically and economically important Mediterranean oaks.

Antibacterial and antibiofilm activity of 1-thiocarbamoyl-3,5-diaryl-4,5-dihydro-1H pyrazoles and thiazoles in multidrug-resistant pathogens - Kamila Furtado da Cunha; Marcelle de Oliveira Garcia; Suzane Olachea Allend; Déborah Trota Farias de Albernaz; Bruno Nunes da Rosa; Isabel Ladeira Pereira; Cláudio Martin de Pereira de Pereira; Daiane Drawanz Hartwig (Brazilian Journal of Microbiology, 2023)

Competitive adsorption of acetaminophen and caffeine onto activated Tingui biochar: characterization, modeling, and mechanisms - Débora Federici dos Santos; Wardleison Martins Moreira; Thiago Peixoto de Araújo; Maria Manuel Serrano Bernardo; Isabel Maria de Figueiredo Ligeiro da Fonseca; Indianara Conceição Ostroski; Maria Angélica Simões Dornellas de Barros (Environmental Science and Pollution Research, 2023)

Emergency cesarean section in dogs: Usefulness of amniotic fluid biochemical parameters and placental morphology as indicators of neonatal viability - Julia Rodrigues Greghi; Phelipe Oliveira Favaron; Luiz Guilherme Corsi Trautwein; Caio Garcia Barbosa da Silva; Gisele Augusta Amorim de Lemos; Maria Isabel Mello Martins (Theriogenology, 2023)

Unravelling and understanding local perceptions of water quality in the Santa basin, Peru - Sally Rangecroft; Rosa Maria Dextre; Isabel Richter; Claudia V. Grados Bueno; Claire Kelly; Cecilia Turin; Beatriz Fuentealba; Mirtha Camacho Hernandez; Sergio Morera; John Martin; Adam Guy; Caroline Clason (Journal of Hydrology, 2023)

The role of values in future scenarios: what types of values underpin (un)sustainable and (un)just futures? - Zuzana V. Harmáčková; Yuki Yoshida; Nadia Sitas; Lelani Mannetti; Adrian Martin; Ritesh Kumar; Marta Berbés-Blázquez; Rebecca Collins; Klaus Eisenack; Ellen Guimaraes; María Heras; Valerie Nelson; et al. (Current Opinion in Environmental Sustainability, 2023)

A comparative proteomics analysis of four contact allergens in THP-1 cells shows distinct alterations in key metabolic pathways - Tessa Höper; Isabel Karkossa; Verónica I. Dumit; Martin von Bergen; Kristin Schubert; Andrea Haase (Toxicology and Applied Pharmacology, 2023)

The Holocene history of grapevine (Vitis vinifera) and viticulture in France retraced from a large-scale archaeobotanical dataset - Laurent Bouby; Lucie Chabal; Vincent Bonhomme; Isabelle Baly; Janet Battentier; Sammy Ben Makhad; Emmanuelle Bonnaire; Manon Cabanis; Cécile Callou; Carine Cenzon-Salvayre; Sylvie Coubray; Geneviève Daoulas; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

The potential of almonds, hazelnuts, and walnuts SFE-CO2 extracts as sources of bread flavouring ingredients - Júlia C. Kessler; Vanessa Vieira; Isabel M. Martins; Yaidelin A. Manrique; Patrícia Ferreira; Ricardo C. Calhelha; Andreia Afonso; Lillian Barros; Alírio E. Rodrigues; Madalena M. Dias (Food Chemistry, 2023)

Xylem formation patterns from Mediterranean to subalpine climate conditions reveal high growth plasticity of pine species on Corsica - Martin Häusser; Sugam Aryal; Johannes A. C. Barth; Jörg Bendix; Emilie Garel; Robert van Geldern; Frédéric Huneau; Tobias R. Juhlke; Isabel Knerr; Sébastien Santoni; Sonja Szymczak; Katja Trachte; et al. (Trees, 2023)
Key message Black pine and Maritime pine exhibit considerable differences in growth phenology across elevation belts with a 1-month delay for xylogenesis and increasing growth rates from low, mid to high elevations. Abstract Investigating seasonal wood formation is crucial to understand tree growth responses to climate impact. The present study quantifies the variability of xylogenesis along an elevation gradient on the Mediterranean island of Corsica, where two native pine species ( Pinus nigra Arnold ssp. laricio Maire and Pinus pinaster Aiton) grow from the upper tree line to sea level, partly in sympatry. We extracted microcores from 35 trees at 5 sites along an East–West transect from the coasts (10 m asl) to the island's central mountain ridge (1600 m asl) during bi-weekly sampling campaigns between 2017 and 2019. We applied generalised additive models to detect radial growth differences in elevation and species along with minimum temperatures for growth initiation. We found that trees in low elevations experienced over 2 months longer growth periods with higher maximum growth rates than in high elevations. The results show a 1-month delay for the beginning of tracheid formation between the low, mid and high-elevation belts but comparable timing for its termination. At the sites where both species co-occur, P. nigra accumulates more radial cells in a shorter time than P. pinaster . Trees at the two contrasting coastal sites have similar growth period lengths, but exhibit a time shift of over a month. Minimum temperatures around growth initiation vary between 3.1 °C for P. nigra and 9.9 °C for P. pinaster . These findings emphasise the high plasticity in the growth behaviour of one of the most widespread tree genera in Mediterranean and temperate zones.

Insights into the fauna associated with Egeria densa at the upper section of the international Minho River estuary (NW Iberian Peninsula) 3 decades after its establishment - Nuno Gomes; Dimítri de Araújo Costa; Duarte Martins; Sónia Rocha; Isabel Sousa-Pinto; Carlos Antunes (Journal of Coastal Conservation, 2023)
The macrophyte Egeria densa Planchon, 1849 is a freshwater plant native to the subtropical regions of South America. Fast vegetative reproduction and efficient dispersal allow this species to form extensive beds that produce high levels of oxygen in freshwater ecosystems, generating microhabitats that act as refuge and nursery for an array of organisms, increasing sedimentation and light availability. Despite its undisputable ecological role, it is considered invasive and is present on all continents except Antarctica with the first records in Europe occurring at the 20th century. At the international Minho River (NW Iberian Peninsula), the observation of its presence was noted in the 1990s and is now an established population in this ecosystem. This study is the first descriptive-taxonomical assessment of the associated fauna with the exotic macrophyte E. densa , using both morphological and molecular approaches, three decades after its establishment in the international Minho River. Results indicate the presence of a faunal assemblage, composed a total of 20 identified species, including platyhelminths, hydrozoans, bryozoans, molluscs (Gastropoda), annelids (Oligochaeta and Hirudinea), crustaceans (Ostracoda, Copepoda, Branchiopoda and Amphipoda), aquatic mites and insects. Paludicella aff. articulata (Ehrenberg, 1831), Girardia sinensis Chen & Wang, 2015, Lebertia insignis Neuman, 1880 and Ceriodaphnia rigaudi Richard 1894 are recorded for the first time in Portugal.

Evolutionary genomics of oceanic island radiations - José Cerca; Darko D. Cotoras; Vanessa C. Bieker; Rishi De-Kayne; Pablo Vargas; Mario Fernández-Mazuecos; Julia López-Delgado; Oliver White; Martin Stervander; Anthony J. Geneva; Juan Ernesto Guevara Andino; Joana Isabel Meier; et al. (Trends in Ecology & Evolution, 2023)

North by northwest: Are unilateral cephalium‐bearing cacti bio‐compasses? - Sinzinando Albuquerque‐Lima; Daniela C. Zappi; Nigel P. Taylor; Martin Lowry; Mats Winberg; Isabel Cristina Machado (Ecology, 2023)

Correlations between product distribution and feedstock composition in thermal cracking processes for mixed plastic waste - Renesteban Forero-Franco; Isabel Cañete-Vela; Teresa Berdugo-Vilches; Judith González-Arias; Jelena Maric; Henrik Thunman; Martin Seemann (Fuel, 2023)

Synthesis and characterization of sustainable polyurethanes from renewable and recycled feedstocks - Eider Mendiburu-Valor; Tamara Calvo-Correas; Loli Martin; Isabel Harismendy; Cristina Peña-Rodriguez; Arantxa Eceiza (Journal of Cleaner Production, 2023)

Thermochemical recycling of tall oil pitch in a dual fluidized bed - Isabel Cañete Vela; Judith González-Arias; Teresa Berdugo Vilches; Martin Seemann; Henrik Thunman (Fuel, 2023)

Effects of chlorine and peroxyacetic acid wash treatments on growth kinetics of Salmonella in fresh-cut lettuce - Sofia Griselda Cuggino; Guiomar Posada-Izquierdo; Isabel Bascón Villegas; Martin Gustavo Theumer; Fernando Pérez-Rodríguez (Food Research International, 2023)

Effects of capping on microbial populations and contaminant immobilization in an old unlined landfill - Alice Kimie Martins Morita; Isabel Kimiko Sakamoto; Maria Bernadete Amancio Varesche; Edson Wendland (Environmental Science and Pollution Research, 2023)

How to use human biomonitoring in chemical risk assessment: Methodological aspects, recommendations, and lessons learned from HBM4EU - Tiina Santonen; Selma Mahiout; Paula Alvito; Petra Apel; Jos Bessems; Wieneke Bil; Teresa Borges; Stephan Bose-O'Reilly; Jurgen Buekers; Ana Isabel Cañas Portilla; Argelia Castaño Calvo; Mercedes de Alba González; et al. (International Journal of Hygiene and Environmental Health, 2023)

Effect of biomass ash on preventing aromatization of olefinic cracking products in dual fluidized bed systems - Judith González-Arias; Teresa Berdugo-Vilches; Chahat Mandviwala; Isabel Cañete-Vela; Martin Seemann; Henrik Thunman (Fuel, 2023)

Paraprobiotic Lacticaseibacillus rhamnosus Protects Intestinal Damage in an Experimental Murine Model of Mucositis - Luísa Martins Trindade; Lícia Torres; Isabel David Matos; Vivian Correia Miranda; Luís Cláudio Lima de Jesus; Gregório Cavalcante; Jonathan Júnio de Souza Oliveira; Geovanni Dantas Cassali; Pamela Mancha-Agresti; Vasco Ariston de Carvalho Azevedo; Tatiani Uceli Maioli; Valbert Nascimento Cardoso; et al. (Probiotics and Antimicrobial Proteins, 2023)

Lack of SARS-CoV-2 RNA evidence in the lungs from wild European polecats (Mustela putorius) from Spain - Guillermo Carmona; Tamara Burgos; Rafael Barrientos; Sara Martin-Garcia; Clara Muñoz; Marta Sánchez-Sánchez; Javier Hernández-Hernández; Carlos Palacín; Pablo Quiles; Alberto Moraga-Fernández; Victor Bandeira; Emilio Virgós; et al. (European Journal of Wildlife Research, 2023)

(Re)Conceptualizing decision-making tools in a risk governance framework for emerging technologies—the case of nanomaterials - Martin Mullins; Martin Himly; Isabel Rodríguez Llopis; Irini Furxhi; Sabine Hofer; Norbert Hofstätter; Peter Wick; Daina Romeo; Dana Küehnel; Kirsi Siivola; Julia Catalán; Kerstin Hund-Rinke; et al. (Environment Systems and Decisions, 2023)
The utility of decision-making tools for the risk governance of nanotechnology is at the core of this paper. Those working in nanotechnology risk management have been prolific in creating such tools, many derived from European FP7 and H2020-funded projects. What is less clear is how such tools might assist the overarching ambition of creating a fair system of risk governance. In this paper, we reflect upon the role that tools might and should play in any system of risk governance. With many tools designed for the risk governance of this emerging technology falling into disuse, this paper provides an overview of extant tools and addresses their potential shortcomings. We also posit the need for a data readiness tool. With the EUs NMP13 family of research consortia about to report to the Commission on ways forward in terms of risk governance of this domain, this is a timely intervention on an important element of any risk governance system.

Atlantic flower–invertebrate interactions: A data set of occurrence and frequency of floral visits - Danilo Boscolo; Bárbara Nobrega Rodrigues; Patrícia Alves Ferreira; Luciano Elsinor Lopes; Vinicius Rodrigues Tonetti; Isabela Cristhina Reis dos Santos; Juliana Akemi Hiruma‐Lima; Laura Nery; Karoline Baptista de Lima; Jéssica Perozi; André Victor Lucci Freitas; Blandina Felipe Viana; et al. (Ecology, 2023)
Encounters between flowers and invertebrates are key events for the functioning of tropical forests. Assessing the structure of networks composed of the interactions between those partners leads to a better understanding of ecosystem functioning and the effects of environmental factors on ecological processes. Gathering such data is, however, costly and time‐consuming, especially in the highly diverse tropics. We aimed to provide a comprehensive repository of available flower–invertebrate interaction information for the Atlantic Forest, a South American tropical forest domain. Data were obtained from published works and “gray literature,” such as theses and dissertations, as well as self‐reports by co‐authors. The data set has ~18,000 interaction records forming 482 networks, each containing between one and 1061 interaction links. Each network was sampled for about 200 h or less, with few exceptions. A total of 641 plant genera within 136 different families and 39 orders were reported, with the most abundant and rich families being Asteraceae, Fabaceae, and Rubiaceae. Invertebrates interacting with these plants were all arthropods from 10 orders, 129 families, and 581 genera, comprising 2419 morphotypes (including 988 named species). Hymenoptera was the most abundant and diverse order, with at least six times more records than the second‐ranked order (Lepidoptera). The complete data set shows Hymenoptera interacting with all plant orders and also shows Diptera, Lepidoptera, Coleoptera, and Hemiptera to be important nodes. Among plants, Asterales and Fabales had the highest number of interactions. The best sampled environment was forest (~8000 records), followed by pastures and crops. Savanna, grasslands, and urban environments (among others) were also reported, indicating a wide range of approaches dedicated to collecting flower–invertebrate interaction data in the Atlantic Forest domain. Nevertheless, most reported data were from forest understory or lower strata, indicating a knowledge gap about flower–invertebrate interactions at the canopy. Also, access to remote regions remains a limitation, generating sampling bias across the geographical range of the Atlantic Forest. Future studies in these continuous and hard‐to‐access forested areas will yield important new information regarding the interactions between flowers and invertebrates in the Atlantic Forest. There are no copyright restrictions on the data set. Please cite this data paper if the data are used in publications and teaching events.

Cistus ladanifer metal uptake and physiological performance in biochar amended mine soils - Bernardo Duarte; Vanessa Pires; João Carreiras; Ricardo Cruz de Carvalho; Renata Ferreira; Manuel F.C. Pereira; António M. Maurício; Susete Martins-Dias; Isabel Caçador (South African Journal of Botany, 2023)

Nitrofurantoin-induced liver injury: long-term follow-up in two prospective DILI registries - Fernando Bessone; Antonella Ferrari; Nelia Hernandez; Manuel Mendizabal; Ezequiel Ridruejo; Alina Zerega; Federico Tanno; Maria Virginia Reggiardo; Julio Vorobioff; Hugo Tanno; Marco Arrese; Vinicius Nunes; et al. (Archives of Toxicology, 2023)
Nitrofurantoin is a synthetic antibiotic that is recommended as first-choice treatment for uncomplicated urinary tract infections. The prescription of this drug has increased dramatically, especially in Latin American countries. We described the demographics, clinical characteristics, biochemical features, and outcome of nitrofurantoin-induced liver injury. We analyzed 23 cases from the Latin American DILI Network (LATINDILI) and the Spanish DILI Registry. Causality was assessed with the RUCAM and RECAM scale. Of the 23 DILI cases included in our series, 96% patients were women, and the mean age of the whole cohort was 61 years. The median time of drug exposure was 175 days (interquartile range [IQR] 96–760), with 11 patients who were prescribed nitrofurantoin for more than six months. Hepatocellular damage was the most frequent pattern of liver injury (83%), and nearly half of the patients had an asymptomatic presentation (52%). Neither death nor liver transplantation was documented in this series. Overall, 65% of the patients ( n = 15) presented with positive autoantibody titres. The median time to resolution was 81 days (IQR 57–141), and 15 patients (83%) recovered within six months. Five patients (22%) developed nitrofurantoin-induced autoimmune-like hepatitis (NI-AILH), of whom two were characterized by a persistent increase in transaminases that required immunosuppressive treatment to achieve normalization of liver enzymes. Clinicians who prescribe nitrofurantoin should be aware that patients who had taken nitrofurantoin for a long term may be at risk of developing nitrofurantoin-induced autoimmune-like hepatitis.

Molecular effects of polystyrene nanoplastics toxicity in zebrafish embryos (Danio rerio) - Raquel Martin-Folgar; Mónica Torres-Ruiz; Mercedes de Alba; Ana Isabel Cañas-Portilla; M Carmen González; Mónica Morales (Chemosphere, 2023)

Heat recovery and water reuse in micro-distilleries improves eco-efficiency of alcohol production - Isabel Schestak; Jan Spriet; Kirsty Black; David Styles; Maria Faragò; Martin Rygaard; A. Prysor Williams (Journal of Environmental Management, 2023)

Characterization of novel of temperate phages of Staphylococcus aureus isolated from bovine milk - Bibiana Martins Barasuol; Juliana Felipetto Cargnelutti; Luis Antônio Sangioni; Daniela Isabel Brayer Pereira; Ana Paula Muterle Varela; Fabiana Quoos Mayer; Emanuele Serro Pottker; Gabriela Flores Gonçalves; Samuel Cibulski; Sônia de Avila Botton (Archives of Microbiology, 2022)

Global patterns in endemicity and vulnerability of soil fungi - Leho Tedersoo; Vladimir Mikryukov; Alexander Zizka; Mohammad Bahram; Niloufar Hagh‐Doust; Sten Anslan; Oleh Prylutskyi; Manuel Delgado‐Baquerizo; Fernando T. Maestre; Jaan Pärn; Maarja Öpik; Mari Moora; et al. (Global Change Biology, 2022)
Fungi are highly diverse organisms, which provide multiple ecosystem services. However, compared with charismatic animals and plants, the distribution patterns and conservation needs of fungi have been little explored. Here, we examined endemicity patterns, global change vulnerability and conservation priority areas for functional groups of soil fungi based on six global surveys using a high‐resolution, long‐read metabarcoding approach. We found that the endemicity of all fungi and most functional groups peaks in tropical habitats, including Amazonia, Yucatan, West‐Central Africa, Sri Lanka, and New Caledonia, with a negligible island effect compared with plants and animals. We also found that fungi are predominantly vulnerable to drought, heat and land‐cover change, particularly in dry tropical regions with high human population density. Fungal conservation areas of highest priority include herbaceous wetlands, tropical forests, and woodlands. We stress that more attention should be focused on the conservation of fungi, especially root symbiotic arbuscular mycorrhizal and ectomycorrhizal fungi in tropical regions as well as unicellular early‐diverging groups and macrofungi in general. Given the low overlap between the endemicity of fungi and macroorganisms, but high conservation needs in both groups, detailed analyses on distribution and conservation requirements are warranted for other microorganisms and soil organisms.

Estimation of mercury emissions from the forest floor of a pine plantation during a wildfire in central Portugal - Alda Maria Domingues Vieira; Maria Vaňková; Isabel Campos; Jakub Trubač; Rafael Baieta; Martin Mihaljevič (Environmental Monitoring and Assessment, 2022)

Involvement of glutamine synthetase 2 (GS2) amplification and overexpression in Amaranthus palmeri resistance to glufosinate - Matheus M. Noguera; Aimone Porri; Isabel S. Werle; James Heiser; Frank Brändle; Jens Lerchl; Brent Murphy; Michael Betz; Fanny Gatzmann; Martin Penkert; Clara Tuerk; Lucie Meyer; et al. (Planta, 2022)
Main conclusion Amplification and overexpression of the target site glutamine synthetase, specifically the plastid-located isoform, confers resistance to glufosinate in Amaranthus palmeri . This mechanism is novel among glufosinate-resistant weeds. Abstract Amaranthus palmeri has recently evolved resistance to glufosinate herbicide. Several A. palmeri populations from Missouri and Mississippi, U.S.A. had survivors when sprayed with glufosinate-ammonium (GFA, 657 g ha −1 ). One population, MO#2 (fourfold resistant) and its progeny (sixfold resistant), were used to study the resistance mechanism, focusing on the herbicide target glutamine synthetase (GS). We identified four GS genes in A. palmeri ; three were transcribed: one coding for the plastidic protein ( GS2 ) and two coding for cytoplasmic isoforms ( GS1.1 and GS1.2 ). These isoforms did not contain mutations associated with resistance. The 17 glufosinate survivors studied showed up to 21-fold increase in GS2 copies. GS2 was expressed up to 190-fold among glufosinate survivors. GS1.1 was overexpressed > twofold in only 3 of 17, and GS1.2 in 2 of 17 survivors. GS inhibition by GFA causes ammonia accumulation in susceptible plants. Ammonia level was analyzed in 12 F1 plants. GS2 expression was negatively correlated with ammonia level ( r = – 0.712); therefore, plants with higher GS2 expression are less sensitive to GFA. The operating efficiency of photosystem II (ϕPSII) of Nicotiana benthamiana overexpressing GS2 was four times less inhibited by GFA compared to control plants. Therefore, increased copy and overexpression of GS2 confer resistance to GFA in A. palmeri (or other plants). We present novel understanding of the role of GS2 in resistance evolution to glufosinate.

Chemical, antioxidant and cytotoxic profile of hydroalcoholic extracts of plants from Southern Brazil and their activity against pathogenic fungi isolated from dogs and cats with sensitivity and resistance to conventional antifungals - Claudia Giordani; Stefanie Bressan Waller; Isabel Martins Madrid; Karina Affedlt Guterres; Caroline Bohnen de Matos; Jessica Fernanda Hoffmann; Luciana Laitano de Castro; Fábio Clasen Chaves; Renata Osório de Faria; Marlete Brum Cleff (Natural Product Research, 2022)

Acaricide activity of the Ximenia americana L. (Olacaceae) stem bark hydroethanolic extract against Rhipicephalus (Boophilus) microplus - Roger Henrique Sousa da Costa; Anita Oliveira Brito Pereira Bezerr Martins; Maria Rayane Correia de Oliveira; Isabel Sousa Alcântara; Felipe Francelino Ferreira; Francisca Fabiana Costa dos Santos; Gyllyandeson de Araújo Delmondes; Francisco Assis Bezerra da Cunha; Henrique Douglas Melo Coutinho; Irwin Rose Alencar de Menezes (Biologia, 2022)

Basidiocarp structures of Lentinus crinitus: an antimicrobial source against foodborne pathogens and food spoilage microorganisms - Míria Benetati Delgado Bertéli; Mariana Martins Magalhães de Souza; Lillian Barros; Isabel C. F. R. Ferreira; Jasmina Glamočlija; Marina Soković; Douglas Cardoso Dragunski; Juliana Silveira do Valle; Ederlan de Souza Ferreira; Laise Cedraz Pinto; Carolina Oliveira de Souza; Suelen Pereira Ruiz; et al. (World Journal of Microbiology and Biotechnology, 2022)

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Brazil’s Amazonian deforestation: the role of landholdings in undesignated public lands - Aurora Miho Yanai; Paulo Maurício Lima de Alencastro Graça; Leonardo Guimarães Ziccardi; Maria Isabel Sobral Escada; Philip Martin Fearnside (Regional Environmental Change, 2022)
The impact of deforestation in Brazilian Amazonia is a global concern, and land occupation in public lands contributes to increased deforestation rates. Little is known about the spread of deforestation in landholdings in undesignated public lands located on cattle-ranching frontiers. We use a case of Matupi District, a hotspot of deforestation along the Transamazon Highway in the southern portion of Brazil’s state of Amazonas, where spontaneous squatters and land grabbers are the main actors occupying landholdings. We assessed the advance of deforestation and the spatial distribution of landholdings in relation to the main road and to land categories (e.g., protected areas and undesignated public land). Landholdings up to 400 ha were the majority in numbers (52%) and larger landholdings (> 400 ha) were located farther into the forest, contributing to expanding the deforestation frontier. By 2018, 80% of the remaining forest was in larger landholdings (> 400 ha), increasing the susceptibility of this forest to being cleared in the coming years. Thus, greater attention should be given to these larger landholdings to control the spread of deforestation. By analyzing the clearing pattern in the landholdings, deforestation monitoring can focus on specific sizes of landholdings that contribute most to the advance of the deforestation frontier. Brazil’s current trend to facilitating the legalization of illegal claims in undesignated public lands, such as the large and medium landholdings we studied, implies vast areas of future deforestation and should be reversed.

Cover Image: Volume 25 Number 3, March 2022 - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)

AVONET: morphological, ecological and geographical data for all birds - Joseph A. Tobias; Catherine Sheard; Alex L. Pigot; Adam J. M. Devenish; Jingyi Yang; Ferran Sayol; Montague H. C. Neate‐Clegg; Nico Alioravainen; Thomas L. Weeks; Robert A. Barber; Patrick A. Walkden; Hannah E. A. MacGregor; et al. (Ecology Letters, 2022)
Functional traits offer a rich quantitative framework for developing and testing theories in evolutionary biology, ecology and ecosystem science. However, the potential of functional traits to drive theoretical advances and refine models of global change can only be fully realised when species‐level information is complete. Here we present the AVONET dataset containing comprehensive functional trait data for all birds, including six ecological variables, 11 continuous morphological traits, and information on range size and location. Raw morphological measurements are presented from 90,020 individuals of 11,009 extant bird species sampled from 181 countries. These data are also summarised as species averages in three taxonomic formats, allowing integration with a global phylogeny, geographical range maps, IUCN Red List data and the eBird citizen science database. The AVONET dataset provides the most detailed picture of continuous trait variation for any major radiation of organisms, offering a global template for testing hypotheses and exploring the evolutionary origins, structure and functioning of biodiversity.

First Case of Brevetoxicosis Linked to Rough-Toothed Dolphin (Steno bredanensis) Mass-Mortality Event in Eastern Central Atlantic Ocean: A Climate Change Effect? - Antonio Fernández; Eva Sierra; Manuel Arbelo; Ana Gago-Martínez; Jose Manuel Leao Martins; Natalia García-Álvarez; Yara Bernaldo de Quiros; Marina Arregui; Ana Isabel Vela; Josue Díaz-Delgado (Frontiers in Marine Science, 2022)
Harmful algal blooms (HABs) have been increasingly recorded over the last decades and much work has linked these events to multiple oceanographic and climate disturbances. HABs can affect ecosystems either as events that affect dissolved oxygen, clog fish gills, or smother corals or through the production of biotoxins which affect living marine resources through food web transfers or aerosols. HAB represent a natural driver of decline and potential extinction of aquatic organisms, from invertebrates to mammals, which may offer little evolutionary adaptation particularly in very high and long-lasting exposures. Despite numerous multispecies mass-mortality events linked to HAB-associated biotoxicosis globally, there are no records in cetaceans off the central eastern Atlantic Ocean. Herein, we report the epidemiology, pathologic, microbiologic and toxicologic investigation results attesting to the first documentation of cetacean mass-mortality in European waters associated with brevetoxins. Twelve rough-toothed dolphins ( Steno bredanensis ) were found dead adrift or beached along the southwestern coast of Gran Canaria from April 28th to May 7th, 2008. Although pathologic examinations were limited by moderate to advanced autolysis and decomposition of the carcasses, consistent findings included multisystemic hemorrhage and undigested ingesta within the gastric compartments, mainly salema porgy ( Sarpa salpa ). Toxicologic analysis of gastric contents identified PbTx2 and PbTx3 brevetoxins. Our results provide compelling toxicopathologic evidence of fatal brevetoxicosis in a cohort of rough-toothed dolphins. These data add to the limited knowledge on pathology of HAB in cetaceans and provide the first account of brevetoxicosis in European waters. No other mass-mortality or individual fatality of any cetacean species has been linked to brevetoxicosis in the Canary Islands since this event.

Clinical and demographic characteristics of patients with functional movement disorders: a consecutive cohort study from a specialized clinic - Celia Delgado; Mónica Kurtis; Beatriz Martin; Pilar Rada; Leticia Martinez; Marta Sanz; Blanca Borda; Carmen Vicente; Montserrat Garcia; Oriol Franch; Isabel Pareés (Acta Neurologica Belgica, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Genetic Variation in ATXN3 (Ataxin-3) 3′UTR: Insights into the Downstream Regulatory Elements of the Causative Gene of Machado-Joseph Disease/Spinocerebellar Ataxia Type 3 - Ana Rosa Vieira Melo; Mafalda Raposo; Marta Ventura; Sandra Martins; Sara Pavão; Isabel Alonso; Conceição Bettencourt; Manuela Lima (The Cerebellum, 2022)

Will borealization of Arctic tundra herbivore communities be driven by climate warming or vegetation change? - James D. M. Speed; J. Adrian Chimal‐Ballesteros; Michael D. Martin; Isabel C. Barrio; Katariina E. M. Vuorinen; Eeva M. Soininen (Global Change Biology, 2021)
Poleward shifts in species distributions are expected and frequently observed with a warming climate. In Arctic ecosystems, the strong warming trends are associated with increasing greenness and shrubification. Vertebrate herbivores have the potential to limit greening and shrub advance and expansion on the tundra, posing the question of whether changes in herbivore communities could partly mediate the impacts of climate warming on Arctic tundra. Therefore, future changes in the herbivore community in the Arctic tundra will depend on whether the community tracks the changing climates directly (i.e. occurs in response to temperature) or indirectly, in response to vegetation changes (which can be modified by trophic interactions). In this study, we used biogeographic and remotely sensed data to quantify spatial variation in vertebrate herbivore communities across the boreal forest and Arctic tundra biomes. We then tested whether present‐day herbivore community structure is determined primarily by temperature or vegetation. We demonstrate that vertebrate herbivore communities are significantly more diverse in the boreal forest than in the Arctic tundra in terms of species richness, phylogenetic diversity and functional diversity. A clear shift in community structure was observed at the biome boundary, with stronger northward declines in diversity in the Arctic tundra. Interestingly, important functional traits characterizing the role of herbivores in limiting tundra vegetation change, such as body mass and woody plant feeding, did not show threshold changes across the biome boundary. Temperature was a more important determinant of herbivore community structure across these biomes than vegetation productivity or woody plant cover. Thus, our study does not support the premise that herbivore‐driven limitation of Arctic tundra shrubification or greening would limit herbivore community change in the tundra. Instead, borealization of tundra herbivore communities is likely to result from the direct effect of climate warming.

Red seaweeds strengthening the nexus between nutrition and health: phytochemical characterization and bioactive properties of Grateloupia turuturu and Porphyra umbilicalis extracts - João Ferreira; Anja Hartmann; Carlos Martins-Gomes; Fernando M. Nunes; Eliana B. Souto; Dario L. Santos; Helena Abreu; Rui Pereira; Mário Pacheco; Isabel Gaivão; Amélia M. Silva (Journal of Applied Phycology, 2021)

Multivariate analysis of factors influencing the peak flow and runoff volume in the Cerrado and Atlantic Forest biomes in Brazil - Línika Vicente Ferreira de Almeida; Leonardo Chinem Kameya; Jovane Martins Correa; Aleska Kaufmann Almeida; Isabel Kaufmann de Almeida (Environmental Monitoring and Assessment, 2021)

Biological activities of the essential oil from the leaves of Lantana montevidensis (Spreng) Briq. in mice - Maria Rayane Correia de Oliveira; Maria Gabriely de Lima Silva; Isabel Sousa Alcântara; Jaime Ribeiro Filho; Cícera Datiane de Morais Oliveira Tintino; Francisco Ernani Alves Magalhães; Anita Oliveira Brito Pereira Bezerr Martins; Renata Torres Pessoa; Antonia Eliene Duarte; José Galberto Martins da Costa; Sidney Gonçalo de Lima; Henrique Douglas Melo Coutinho; et al. (Environment, Development and Sustainability, 2021)

Species loss due to nutrient addition increases with spatial scale in global grasslands - Eric W. Seabloom; Evan Batzer; Jonathan M. Chase; W. Stanley Harpole; Peter B. Adler; Sumanta Bagchi; Jonathan D. Bakker; Isabel C. Barrio; Lori Biederman; Elizabeth H. Boughton; Miguel N. Bugalho; Maria C. Caldeira; et al. (Ecology Letters, 2021)
The effects of altered nutrient supplies and herbivore density on species diversity vary with spatial scale, because coexistence mechanisms are scale dependent. This scale dependence may alter the shape of the species–area relationship (SAR), which can be described by changes in species richness ( S ) as a power function of the sample area ( A ): S = cA z , where c and z are constants. We analysed the effects of experimental manipulations of nutrient supply and herbivore density on species richness across a range of scales (0.01–75 m 2 ) at 30 grasslands in 10 countries. We found that nutrient addition reduced the number of species that could co‐occur locally, indicated by the SAR intercepts (log c ), but did not affect the SAR slopes ( z ). As a result, proportional species loss due to nutrient enrichment was largely unchanged across sampling scales, whereas total species loss increased over threefold across our range of sampling scales.

Genome sequencing in families with congenital limb malformations - Jonas Elsner; Martin A. Mensah; Manuel Holtgrewe; Jakob Hertzberg; Stefania Bigoni; Andreas Busche; Marie Coutelier; Deepthi C. de Silva; Nursel Elçioglu; Isabel Filges; Erica Gerkes; Katta M. Girisha; et al. (Human Genetics, 2021)
The extensive clinical and genetic heterogeneity of congenital limb malformation calls for comprehensive genome-wide analysis of genetic variation. Genome sequencing (GS) has the potential to identify all genetic variants. Here we aim to determine the diagnostic potential of GS as a comprehensive one-test-for-all strategy in a cohort of undiagnosed patients with congenital limb malformations. We collected 69 cases (64 trios, 1 duo, 5 singletons) with congenital limb malformations with no molecular diagnosis after standard clinical genetic testing and performed genome sequencing. We also developed a framework to identify potential noncoding pathogenic variants. We identified likely pathogenic/disease-associated variants in 12 cases (17.4%) including four in known disease genes, and one repeat expansion in HOXD13 . In three unrelated cases with ectrodactyly, we identified likely pathogenic variants in UBA2 , establishing it as a novel disease gene. In addition, we found two complex structural variants (3%). We also identified likely causative variants in three novel high confidence candidate genes. We were not able to identify any noncoding variants. GS is a powerful strategy to identify all types of genomic variants associated with congenital limb malformation, including repeat expansions and complex structural variants missed by standard diagnostic approaches. In this cohort, no causative noncoding SNVs could be identified.

Connecting tree‐ring phenotypes, genetic associations and transcriptomics to decipher the genomic architecture of drought adaptation in a widespread conifer - Claire Depardieu; Sébastien Gérardi; Simon Nadeau; Geneviève J. Parent; John Mackay; Patrick Lenz; Manuel Lamothe; Martin P. Girardin; Jean Bousquet; Nathalie Isabel (Molecular Ecology, 2021)
As boreal forests face significant threats from climate change, understanding evolutionary trajectories of coniferous species has become fundamental to adapting management and conservation to a drying climate. We examined the genomic architecture underlying adaptive variation related to drought tolerance in 43 populations of a widespread boreal conifer, white spruce ( Picea glauca [Moench] Voss), by combining genotype–environment associations, genotype–phenotype associations, and transcriptomics. Adaptive genetic variation was identified by correlating allele frequencies for 6,153 single nucleotide polymorphisms from 2,606 candidate genes with temperature, precipitation and aridity gradients, and testing for significant associations between genotypes and 11 dendrometric and drought‐related traits (i.e., anatomical, growth response and climate‐sensitivity traits) using a polygenic model. We identified a set of 285 genes significantly associated with a climatic factor or a phenotypic trait, including 110 that were differentially expressed in response to drought under greenhouse‐controlled conditions. The interlinked phenotype–genotype–environment network revealed eight high‐confidence genes involved in white spruce adaptation to drought, of which four were drought‐responsive in the expression analysis. Our findings represent a significant step toward the characterization of the genomic basis of drought tolerance and adaptation to climate in conifers, which is essential to enable the establishment of resilient forests in view of new climate conditions.

Anthropogenic impact on the historical phytoplankton community of Lake Constance reconstructed by multimarker analysis of sediment‐core environmental DNA - Anan Ibrahim; Eric Capo; Martin Wessels; Isabel Martin; Axel Meyer; David Schleheck; Laura S. Epp (Molecular Ecology, 2021)
During the 20th century, many lakes in the Northern Hemisphere were affected by increasing human population and urbanization along their shorelines and catchment, resulting in aquatic eutrophication. Ecosystem monitoring commenced only after the changes became apparent, precluding any examination of timing and dynamics of initial community change in the past and comparison of pre‐ and postimpact communities. Peri‐Alpine Lake Constance (Germany) underwent a mid‐century period of eutrophication followed by re‐oligotrophication since the 1980s and is now experiencing warm temperatures. We extended the period for which monitoring data of indicator organisms exist by analysing historical environmental DNA (eDNA) from a sediment core dating back some 110 years. Using three metabarcoding markers—for microbial eukaryotes, diatoms and cyanobacteria—we revealed two major breakpoints of community change, in the 1930s and the mid‐1990s. In our core, the latest response was exhibited by diatoms, which are classically used as palaeo‐bioindicators for the trophic state of lakes. Following re‐oligotrophication, overall diversity values reverted to similar ones of the early 20th century, but multivariate analysis indicated that the present community is substantially dissimilar. Community changes of all three groups were strongly correlated to phosphorus concentration changes, whereas significant relationships to temperature were only observed when we did not account for temporal autocorrelation. Our results indicate that each microbial group analysed exhibited a unique response, highlighting the particular strength of multimarker analysis of eDNA, which is not limited to organisms with visible remains and can therefore discover yet unknown responses and abiotic–biotic relationships.

Cerebral hemodynamics in obesity: relationship with sex, age, and adipokines in a cohort-based study - Oscar Ayo-Martin; Jorge García-García; Francisco Hernández-Fernández; Mercedes Gómez-Hontanilla; Isabel Gómez-Fernández; Carolina Andrés-Fernández; Cristina Lamas; José Joaquín Alfaro-Martínez; Francisco Botella; Tomás Segura (GeroScience, 2021)

(Sub)urban gardens from Provence (Southern France, 14th–17th century) and the presence of Ricinus communis - Isabel Figueiral; Pascale Chevillot; Sophie Martin; Sarah Ivorra; Françoise Paone; Elsa Sagetat-Basseuil; Brigitte de-Luca; Josiane Cuzon (Vegetation History and Archaeobotany, 2021)

Geographic distribution of the Ipomoea batatas (Convolvulaceae) pest, Bedellia somnulentella (Zeller) (Lepidoptera: Bedelliidae), in Minas Gerais state, Brazil - Marinalva Martins dos Santos; Gleisiany Nunes Gomes; Thiago Almeida Andrade Pinto; Isabel Moreira da Silva; Germano Leão Demolin Leite; Marcus Alvarenga Soares (Journal of Plant Diseases and Protection, 2021)

Susceptibility and resistance of Sporothrix brasiliensis to branded and compounded itraconazole formulations - Stefanie Bressan Waller; Márcia Kutscher Ripoll; Isabel Martins Madrid; Tanize Acunha; Marlete Brum Cleff; Fábio Clasen Chaves; João Roberto Braga de Mello; Renata Osório de Faria; Mário Carlos Araújo Meireles (Brazilian Journal of Microbiology, 2021)

Estimate the effects of environmental determining factors on childhood asthma hospital admissions in Lisbon, Portugal: a time series modelling study - Mónica Rodrigues; Isabel Natário; Maria do Rosário de Oliveira Martins (Theoretical and Applied Climatology, 2021)

Chronic stress decreases ornithine decarboxylase expression and protects against 1,2-dimethylhydrazine-induced colon carcinogenesis - Edgar Oswaldo Zamora-González; Patricia Castro-Félix; María del Rosario Huizar-López; Josefina Casas-Solís; María de la Luz Blanca Isabel Marques-González; Martha Fabiola Martin del Campo-Solís; Anne Santerre (Molecular Biology Reports, 2020)

Microbial structure and diversity in non-sanitary landfills and association with physicochemical parameters - Alice Kimie Martins Morita; Isabel Kimiko Sakamoto; Maria Bernadete Amancio Varesche; Edson Wendland (Environmental Science and Pollution Research, 2020)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Getting ahead: exploitative competition by an invasive lizard - Isabel Damas-Moreira; Julia L. Riley; Miguel A. Carretero; D. James Harris; Martin J. Whiting (Behavioral Ecology and Sociobiology, 2020)

Adaptive and maladaptive genetic diversity in small populations: Insights from the Brook Charr ( Salvelinus fontinalis ) case study - Anne‐Laure Ferchaud; Maeva Leitwein; Martin Laporte; Damien Boivin‐Delisle; Bérénice Bougas; Cécilia Hernandez; Éric Normandeau; Isabel Thibault; Louis Bernatchez (Molecular Ecology, 2020)
Investigating the relative importance of neutral versus selective processes governing the accumulation of genetic variants is a key goal in both evolutionary and conservation biology. This is particularly true in the context of small populations, where genetic drift can counteract the effect of selection. Using Brook Charr ( Salvelinus fontinalis ) from Québec, Canada, as a case study, we investigated the importance of demographic versus selective processes governing the accumulation of both adaptive and maladaptive mutations in closed versus open and connected populations to assess gene flow effect. This was achieved by using 14,779 high‐quality filtered SNPs genotyped among 1,416 fish representing 50 populations from three life history types: lacustrine (closed populations), riverine and anadromous (connected populations). Using the PROVEAN algorithm, we observed a considerable accumulation of putative deleterious mutations across populations. The absence of correlation between the occurrence of putatively beneficial or deleterious mutations and local recombination rate supports the hypothesis that genetic drift might be the main driver of the accumulation of such variants. However, despite a lower genetic diversity observed in lacustrine than in riverine or anadromous populations, lacustrine populations do not exhibit more deleterious mutations than the two other history types, suggesting that the negative effect of genetic drift in lacustrine populations may be mitigated by that of relaxed purifying selection. Moreover, we also identified genomic regions associated with anadromy, as well as an overrepresentation of transposable elements associated with variation in environmental variables, thus supporting the importance of transposable elements in adaptation.

Length Polymorphisms in the Angiotensin I-Converting Enzyme Gene and the Serotonin-Transporter-Linked Polymorphic Region Constitute a Risk Haplotype for Depression in Patients with Coronary Artery Disease - Thomas Meyer; Isabel Rothe; Julia Staab; Hans-Christian Deter; Stella V. Fangauf; Stefanie Hamacher; Martin Hellmich; Jana Jünger; Karl-Heinz Ladwig; Matthias Michal; Katja Petrowski; Joram Ronel; et al. (Biochemical Genetics, 2020)
Genetic variations affecting the course of depressive symptoms in patients with coronary artery disease (CAD) have not yet been well studied. Therefore, we set out to investigate whether distinct haplotypes of the two insertion/deletion polymorphisms in the serotonin-transporter-linked polymorphic region ( 5-HTTLPR ) and the angiotensin I-converting enzyme ( ACE ) gene located on chromosome 17 can be identified as risk factors for trajectories of depression. Clinical and genotyping data were derived from 507 depressed CAD patients participating in the randomized, controlled, multicenter Stepwise Psychotherapy Intervention for Reducing Risk in Coronary Artery Disease (SPIRR-CAD) trial, of whom the majority had an acute cardiac event before study inclusion. Depression scores on the Hospital Anxiety and Depression Scale (HADS) were assessed at baseline and at five follow-up time points up to 2 years after study entrance. At baseline, depression scores did not significantly differ between patients carrying the risk haplotype ACE D/D, 5-HTTLPR I/I ( n = 46) and the non-risk haplotypes ( n = 461, 10.9 ± 2.7 versus 10.4 ± 2.5, p = 0.254). HADS-depression scores declined from study inclusion during the first year irrespective of the genotype. At each follow-up time point, HADS-depression scores were significantly higher in ACE D/D, 5-HTTLPR I/I carriers than in their counterparts. Two years after study inclusion, the mean HADS depression score remained 1.8 points higher in patients with the risk haplotype as compared to subjects not carrying this haplotype (9.9 ± 4.2 versus 8.1 ± 4.0, p = 0.009). In summary, the presence of the ACE D/D, 5-HTTLPR I/I haplotype may be a vulnerability factor for comorbid depressive symptoms in CAD patients.

Strong overestimation of water‐use efficiency responses to rising CO 2 in tree‐ring studies - William Marchand; Martin P. Girardin; Henrik Hartmann; Claire Depardieu; Nathalie Isabel; Sylvie Gauthier; Étienne Boucher; Yves Bergeron (Global Change Biology, 2020)
The carbon isotope ratio (δ 13 C) in tree rings is commonly used to derive estimates of the assimilation‐to‐stomatal conductance rate of trees, that is, intrinsic water‐use efficiency (iWUE). Recent studies have observed increased iWUE in response to rising atmospheric CO 2 concentrations ( C a ), in many different species, genera and biomes. However, increasing rates of iWUE vary widely from one study to another, likely because numerous covarying factors are involved. Here, we quantified changes in iWUE of two widely distributed boreal conifers using tree samples from a forest inventory network that were collected across a wide range of growing conditions (assessed using the site index, SI), developmental stages and stand histories. Using tree‐ring isotopes analysis, we assessed the magnitude of increase in iWUE after accounting for the effects of tree size, stand age, nitrogen deposition, climate and SI. We also estimated how growth conditions have modulated tree physiological responses to rising C a . We found that increases in tree size and stand age greatly influenced iWUE. The effect of C a on iWUE was strongly reduced after accounting for these two variables. iWUE increased in response to C a , mostly in trees growing on fertile stands, whereas iWUE remained almost unchanged on poor sites. Our results suggest that past studies could have overestimated the CO 2 effect on iWUE, potentially leading to biased inferences about the future net carbon balance of the boreal forest. We also observed that this CO 2 effect is weakening, which could affect the future capacity of trees to resist and recover from drought episodes.

Global gradients in intraspecific variation in vegetative and floral traits are partially associated with climate and species richness - Jonas Kuppler; Cécile H. Albert; Gregory M. Ames; William Scott Armbruster; Gerhard Boenisch; Florian C. Boucher; Diane R. Campbell; Liedson T. Carneiro; Eduardo Chacón‐Madrigal; Brian J. Enquist; Carlos R. Fonseca; José M. Gómez; et al. (Global Ecology and Biogeography, 2020)
Aim Intraspecific trait variation (ITV) within natural plant communities can be large, influencing local ecological processes and dynamics. Here, we shed light on how ITV in vegetative and floral traits responds to large‐scale abiotic and biotic gradients (i.e., climate and species richness). Specifically, we tested whether associations of ITV with temperature, precipitation and species richness were consistent with any of four hypotheses relating to stress tolerance and competition. Furthermore, we estimated the degree of correlation between ITV in vegetative and floral traits and how they vary along the gradients. Location Global. Time period 1975–2016. Major taxa studied Herbaceous and woody plants. Methods We compiled a dataset of 18,401 measurements of the absolute extent of ITV (measured as the coefficient of variation) in nine vegetative and seven floral traits from 2,822 herbaceous and woody species at 2,372 locations. Results Large‐scale associations between ITV and climate were trait specific and more prominent for vegetative traits, especially leaf morphology, than for floral traits. The ITV showed pronounced associations with climate, with lower ITV values in colder areas and higher values in drier areas. The associations of ITV with species richness were inconsistent across traits. Species‐specific associations across gradients were often idiosyncratic, and covariation in ITV was weaker between vegetative and floral traits than within the two trait groups. Main conclusions Our results show that, depending on the traits considered, ITV either increased or decreased with climate stress and species richness, suggesting that both factors can constrain or enhance ITV, which might foster plant‐population persistence in stressful conditions. Given the species‐specific responses and covariation in ITV, associations can be hard to predict for traits and species not yet studied. We conclude that consideration of ITV can improve our understanding of how plants cope with stressful conditions and environmental change across spatial and biological scales.

Downscaling projections of climate change in Sao Tome and Principe Islands, Africa - Sin Chan Chou; André de Arruda Lyra; Jorge Luís Gomes; Daniel Andrés Rodriguez; Minella Alves Martins; Nicole Costa Resende; Priscila da Silva Tavares; Claudine Pereira Dereczynski; Isabel Lopes Pilotto; Alessandro Marques Martins; Luís Felipe Alves de Carvalho; José Luiz Lima Onofre; et al. (Climate Dynamics, 2020)

Circumpolar terrestrial arthropod monitoring: A review of ongoing activities, opportunities and challenges, with a focus on spiders - Mark A. K. Gillespie; Matthias Alfredsson; Isabel C. Barrio; Joe Bowden; Peter Convey; Stephen J. Coulson; Lauren E. Culler; Martin T. Dahl; Kathryn M. Daly; Seppo Koponen; Sarah Loboda; Yuri Marusik; et al. (Ambio, 2020)

A revision of the African genus Mesanthemum (Eriocaulaceae) - Yuxi Liang; Sylvia M. Phillips; Martin Cheek; Isabel Larridon (Kew Bulletin, 2019)
Summary Mesanthemum is a genus comprising 16 species in the family Eriocaulaceae and is native to Africa and Madagascar. Eriocaulaceae are characterised by a basal tuft or rosette of narrow leaves and small flowers in heads. Mesanthemum can be recognised by diplostemonous flowers and fused glandular pistillate petals. While most Mesanthemum species are large perennial herbs, two small ephemeral species from West Africa, M. albidum and M. auratum differ from the rest of the genus by their shorter life cycle, smaller size, simpler floral structures and different seed surface patterning. A molecular phylogenetic study, morphological comparisons and scanning electron microscope (SEM) examination of seed coat sculpture were carried out to determine whether they should be separated as a new genus. The molecular results indicate that the two ephemeral species are nested in the Mesanthemum clade. However, they are not closely related to each other. All species of Mesanthemum are here revised, including the description of a new species M. alenicola from Equatorial Guinea. An identification key is provided, together with taxonomic descriptions, synonymy and notes. Images of the seeds as seen under SEM are provided where available. Lectotypifications are provided for Mesanthemum albidum , M. bennae , M. pilosum , M. prescottianum , M. pubescens and M. variabile . A neotype is selected for M. rutenbergianum , which is synonymised with M. pubescens .

Global warming impact on confined livestock in buildings: efficacy of adaptation measures to reduce heat stress for growing-fattening pigs - Günther Schauberger; Christian Mikovits; Werner Zollitsch; Stefan J. Hörtenhuber; Johannes Baumgartner; Knut Niebuhr; Martin Piringer; Werner Knauder; Ivonne Anders; Konrad Andre; Isabel Hennig-Pauka; Martin Schönhart (Climatic Change, 2019)

Spatio‐temporal patterns of tree growth as related to carbon isotope fractionation in European forests under changing climate - Tatiana A. Shestakova; Jordi Voltas; Matthias Saurer; Frank Berninger; Jan Esper; Laia Andreu‐Hayles; Valérie Daux; Gerhard Helle; Markus Leuenberger; Neil J. Loader; Valérie Masson‐Delmotte; Antonio Saracino; et al. (Global Ecology and Biogeography, 2019)
Aim The aim was to decipher Europe‐wide spatio‐temporal patterns of forest growth dynamics and their associations with carbon isotope fractionation processes inferred from tree rings as modulated by climate warming. Location Europe and North Africa (30‒70° N, 10° W‒35° E). Time period 1901‒2003. Major taxa studied Temperate and Euro‐Siberian trees. Methods We characterize changes in the relationship between tree growth and carbon isotope fractionation over the 20th century using a European network consisting of 20 site chronologies. Using indexed tree‐ring widths (TRW i ), we assess shifts in the temporal coherence of radial growth across sites (synchrony) for five forest ecosystems (Atlantic, boreal, cold continental, Mediterranean and temperate). We also examine whether TRW i shows variable coupling with leaf‐level gas exchange, inferred from indexed carbon isotope discrimination of tree‐ring cellulose (Δ 13 C i ). Results We find spatial autocorrelation for TRW i and Δ 13 C i extending over a maximum of 1,000 km among forest stands. However, growth synchrony is not uniform across Europe, but increases along a latitudinal gradient concurrent with decreasing temperature and evapotranspiration. Latitudinal relationships between TRW i and Δ 13 C i (changing from negative to positive southwards) point to drought impairing carbon uptake via stomatal regulation for water saving occurring at forests below 60° N in continental Europe. An increase in forest growth synchrony over the 20th century together with increasingly positive relationships between TRW i and Δ 13 C i indicate intensifying impacts of drought on tree performance. These effects are noticeable in drought‐prone biomes (Mediterranean, temperate and cold continental). Main conclusions At the turn of this century, convergence in growth synchrony across European forest ecosystems is coupled with coordinated warming‐induced effects of drought on leaf physiology and tree growth spreading northwards. Such a tendency towards exacerbated moisture‐sensitive growth and physiology could override positive effects of enhanced leaf intercellular CO 2 concentrations, possibly resulting in Europe‐wide declines of forest carbon gain in the coming decades.

Epidemiology and clinical impact of viral, atypical, and fungal respiratory pathogens in symptomatic immunocompromised patients: a two-center study using a multi-parameter customized respiratory Taqman® array card - Deborah Steensels; Marijke Reynders; Patrick Descheemaeker; Martin D. Curran; Maya Hites; Isabelle Etienne; Isabel Montesinos (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

An Integrated All-Atlantic Ocean Observing System in 2030 - Brad deYoung; Martin Visbeck; Moacyr Cunha de Araujo Filho; Molly O’Neil Baringer; CarolAnne Black; Erik Buch; Gabrielle Canonico; Paulo Coelho; Janice T. Duha; Martin Edwards; Albert Fischer; Jan-Stefan Fritz; et al. (Frontiers in Marine Science, 2019)

Global Observational Needs and Resources for Marine Biodiversity - Gabrielle Canonico; Pier Luigi Buttigieg; Enrique Montes; Frank E. Muller-Karger; Carol Stepien; Dawn Wright; Abigail Benson; Brian Helmuth; Mark Costello; Isabel Sousa-Pinto; Hanieh Saeedi; Jan Newton; et al. (Frontiers in Marine Science, 2019)

From Observation to Information and Users: The Copernicus Marine Service Perspective - Pierre Yves Le Traon; Antonio Reppucci; Enrique Alvarez Fanjul; Lotfi Aouf; Arno Behrens; Maria Belmonte; Abderrahim Bentamy; Laurent Bertino; Vittorio Ernesto Brando; Matilde Brandt Kreiner; Mounir Benkiran; Thierry Carval; et al. (Frontiers in Marine Science, 2019)

Macroalgal responses to coastal urbanization: relative abundance of indicator species - Edson Régis Tavares Pessoa Pinho de Vasconcelos; Juliane Bernardi Vasconcelos; Thiago Nogueira de Vasconcelos Reis; Adilma de Lourdes Montenegro Cocentino; Arsenio José Areces Mallea; Gustavo M. Martins; Ana Isabel Neto; Mutue Toyota Fujii (Journal of Applied Phycology, 2019)

Impacts of global warming on confined livestock systems for growing-fattening pigs: simulation of heat stress for 1981 to 2017 in Central Europe - Christian Mikovits; Werner Zollitsch; Stefan J. Hörtenhuber; Johannes Baumgartner; Knut Niebuhr; Martin Piringer; Ivonne Anders; Konrad Andre; Isabel Hennig-Pauka; Martin Schönhart; Günther Schauberger (International Journal of Biometeorology, 2019)

Migratory birds as vehicles for parasite dispersal? Infection by avian haemosporidians over the year and throughout the range of a long‐distance migrant - Paulo C. Pulgarín‐R; Camila Gómez; Nicholas J. Bayly; Staffan Bensch; Alyssa M. FitzGerald; Naima Starkloff; Jeremy J. Kirchman; Ana M. González‐Prieto; Keith A. Hobson; Judit Ungvari‐Martin; Heather Skeen; María Isabel Castaño; et al. (Journal of Biogeography, 2019)
Aim The role of migratory birds in the spread of parasites is poorly known, in part because migratory strategies and behaviours potentially affecting transmission are not easy to study. We investigated the dynamics of infection by blood parasites through the annual cycle of a long‐distance Nearctic–Neotropical migratory songbird to examine the role of this species in dispersing parasites between continents. Location The Americas. Taxon Grey‐cheeked Thrush ( Catharus minimus , Aves, Passeriformes, Turdidae), Birds. Methods We used molecular and microscopy screening of haemosporidian parasites ( Plasmodium , Haemoproteus , and Leucocytozoon ) to examine the prevalence, distribution, and diversity of lineages through the annual cycle (breeding, migration, and wintering) of the grey‐cheeked thrush in North and Central America, Santa Marta mountains, the Andes, and the Amazon. We aimed to identify transmission areas, to examine the degree of sharing of haemosporidian lineages with resident birds in various areas and to assess the potential role of immunologically naïve juvenile individuals in parasite transmission. Results Prevalence and lineage diversity of haemosporidians varied significantly over time, being higher during breeding and fall and spring migration, and declining during wintering. Grey‐cheeked thrush shared few parasite lineages with tropical resident birds and slightly more lineages with other migratory and resident boreal species. We detected gametocytes in blood during spring migration stopover, but these were of lineages not found in resident tropical birds, indicating relapses of parasites transmitted elsewhere. Transmission likely occurs mostly on the breeding grounds, where juveniles and adults carried lineages restricted to closely related species of thrushes and other species of boreal birds. Main conclusions Long‐distance migratory songbirds are likely not important dispersers of blood parasites because there are ecological and evolutionary barriers to the interchange of parasites across vastly separated areas. Further work with thorough spatial and temporal sampling across other species, and considering the role of vectors, is necessary to understand the ecological and evolutionary factors explaining the distribution of parasites over broad scales.

A key to the species of Keetia (Rubiaceae - Vanguerieae) in West Africa, with three new, threatened species from Guinea and Ivory Coast - Martin Cheek; Sekou Magassouba; Denise Molmou; Tokpa Seny Doré; Charlotte Couch; Shigeo Yasuda; Charlie Gore; Amy Guest; Aurelie Grall; Isabel Larridon; Isabelle H. Bousquet; Bella Ganatra; et al. (Kew Bulletin, 2018)

Climatically controlled reproduction drives interannual growth variability in a temperate tree species - Andrew J. Hacket‐Pain; Davide Ascoli; Giorgio Vacchiano; Franco Biondi; Liam Cavin; Marco Conedera; Igor Drobyshev; Isabel Dorado Liñán; Andrew D. Friend; Michael Grabner; Claudia Hartl; Juergen Kreyling; et al. (Ecology Letters, 2018)
Climatically controlled allocation to reproduction is a key mechanism by which climate influences tree growth and may explain lagged correlations between climate and growth. We used continent‐wide datasets of tree‐ring chronologies and annual reproductive effort in Fagus sylvatica from 1901 to 2015 to characterise relationships between climate, reproduction and growth. Results highlight that variable allocation to reproduction is a key factor for growth in this species, and that high reproductive effort (‘mast years’) is associated with stem growth reduction. Additionally, high reproductive effort is associated with previous summer temperature, creating lagged climate effects on growth. Consequently, understanding growth variability in forest ecosystems requires the incorporation of reproduction, which can be highly variable. Our results suggest that future response of growth dynamics to climate change in this species will be strongly influenced by the response of reproduction.

Contribution of Eisenia andrei earthworms in pathogen reduction during vermicomposting - Petra Procházková; Aleš Hanč; Jiří Dvořák; Radka Roubalová; Markéta Drešlová; Tereza Částková; Vladimír Šustr; František Škanta; Natividad Isabel Navarro Pacheco; Martin Bilej (Environmental Science and Pollution Research, 2018)

Publisher Correction to: Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome - Isabel C. Barrio; Elin Lindén; Mariska Te Beest; Johan Olofsson; Adrian Rocha; Eeva M. Soininen; Juha M. Alatalo; Tommi Andersson; Ashley Asmus; Julia Boike; Kari Anne Bråthen; John P. Bryant; et al. (Polar Biology, 2018)

Amniotic membrane extract differentially regulates human peripheral blood T cell subsets, monocyte subpopulations and myeloid dendritic cells - Paula Laranjeira; Marta Duque; Martin Vojtek; Maria J. Inácio; Isabel Silva; Ana C. Mamede; Mafalda Laranjo; Susana Pedreiro; Maria J. Carvalho; Paulo Moura; Ana M. Abrantes; Cláudio J. Maia; et al. (Cell and Tissue Research, 2018)

Screening for germline mutations in mismatch repair genes in patients with Lynch syndrome by next generation sequencing - Barbara Luísa Soares; Ayslan Castro Brant; Renan Gomes; Tatiane Pastor; Naye Balzan Schneider; Ândrea Ribeiro-dos-Santos; Paulo Pimentel de Assumpção; Maria Isabel W. Achatz; Patrícia Ashton-Prolla; Miguel Angelo Martins Moreira (Familial Cancer, 2018)

Advancing Marine Biological Observations and Data Requirements of the Complementary Essential Ocean Variables (EOVs) and Essential Biodiversity Variables (EBVs) Frameworks - Frank E. Muller-Karger; Patricia Miloslavich; Nicholas J. Bax; Samantha Simmons; Mark J. Costello; Isabel Sousa Pinto; Gabrielle Canonico; Woody Turner; Michael Gill; Enrique Montes; Benjamin D. Best; Jay Pearlman; et al. (Frontiers in Marine Science, 2018)

Climate Change Impacts on Seagrass Meadows and Macroalgal Forests: An Integrative Perspective on Acclimation and Adaptation Potential - Bernardo Duarte; Irene Martins; Rui Rosa; Ana R. Matos; Michael Y. Roleda; Thorsten B. H. Reusch; Aschwin H. Engelen; Ester A. Serrão; Gareth A. Pearson; João C. Marques; Isabel Caçador; Carlos M. Duarte; et al. (Frontiers in Marine Science, 2018)

Movement Patterns Differ between Sexes and Depend on Weather Conditions in the Butterfly Lycaena tityrus - Elisabeth Reim; Ingo Arnstedt; Isabel Barwisch; Max Baumgarten; Sascha Bock; Julia Eberspach; Julia Ellerbrok; Mulugeta Gebremeskel; Simon Küpper; Lukas Guth; Aninha Lassen; Letro Letro; et al. (Journal of Insect Behavior, 2018)

BacHBerry: BACterial Hosts for production of Bioactive phenolics from bERRY fruits - Alexey Dudnik; A. Filipa Almeida; Ricardo Andrade; Barbara Avila; Pilar Bañados; Diane Barbay; Jean-Etienne Bassard; Mounir Benkoulouche; Michael Bott; Adelaide Braga; Dario Breitel; Rex Brennan; et al. (Phytochemistry Reviews, 2018)

Fungal Olecranon Bursitis in an Immunocompetent Patient by Knoxdaviesia dimorphospora sp. nov.: Case Report and Review - Marcela Guevara-Suarez; Marta Llaurado; Isabel Pujol; Emilio Mayayo; Adela Martin-Vicente; Josepa Gené (Mycopathologia, 2018)

Background invertebrate herbivory on dwarf birch (Betula glandulosa-nana complex) increases with temperature and precipitation across the tundra biome - Isabel C. Barrio; Elin Lindén; Mariska Te Beest; Johan Olofsson; Adrian Rocha; Eeva M. Soininen; Juha M. Alatalo; Tommi Andersson; Ashley Asmus; Julia Boike; Kari Anne Bråthen; John P. Bryant; et al. (Polar Biology, 2017)

Gene expression and activity of antioxidant enzymes in rice plants, cv. BRS AG, under saline stress - Tatiana Rossatto; Marcelo Nogueira do Amaral; Letícia Carvalho Benitez; Isabel Lopes Vighi; Eugenia Jacira Bolacel Braga; Ariano Martins de Magalhães Júnior; Mara Andrade Colares Maia; Luciano da Silva Pinto (Physiology and Molecular Biology of Plants, 2017)

Production of Electrospun Fast-Dissolving Drug Delivery Systems with Therapeutic Eutectic Systems Encapsulated in Gelatin - Francisca Mano; Marta Martins; Isabel Sá-Nogueira; Susana Barreiros; João Paulo Borges; Rui L. Reis; Ana Rita C. Duarte; Alexandre Paiva (AAPS PharmSciTech, 2017)

Multiphysics Modeling of the Atrial Systole under Standard Ablation Strategies - Julia M. Hörmann; Cristóbal Bertoglio; Andreas Nagler; Martin R. Pfaller; Felix Bourier; Martin Hadamitzky; Isabel Deisenhofer; Wolfgang A. Wall (Cardiovascular Engineering and Technology, 2017)

Using early life stages of marine animals to screen the toxicity of priority hazardous and noxious substances - Isabel Cunha; Tiago Torres; Helena Oliveira; Rosário Martins; Thomas McGowan; David Sheahan; Miguel Machado Santos (Environmental Science and Pollution Research, 2017)

Desulfovibrio vulgaris CbiK P cobaltochelatase: evolution of a haem binding protein orchestrated by the incorporation of two histidine residues - Susana A.L. Lobo; Marco A.M. Videira; Isabel Pacheco; Mark N. Wass; Martin J. Warren; Miguel Teixeira; Pedro M. Matias; Célia V. Romão; Lígia M. Saraiva (Environmental Microbiology, 2017)
Summary The sulfate‐reducing bacteria of the Desulfovibrio genus make three distinct modified tetrapyrroles, haem, sirohaem and adenosylcobamide, where sirohydrochlorin acts as the last common biosynthetic intermediate along the branched tetrapyrrole pathway. Intriguingly, D. vulgaris encodes two sirohydrochlorin chelatases, CbiK P and CbiK C , that insert cobalt/iron into the tetrapyrrole macrocycle but are thought to be distinctly located in the periplasm and cytoplasm respectively. Fusing GFP onto the C‐terminus of CbiK P confirmed that the protein is transported to the periplasm. The structure‐function relationship of CbiK P was studied by constructing eleven site‐directed mutants and determining their chelatase activities, oligomeric status and haem binding abilities. Residues His154 and His216 were identified as essential for metal‐chelation of sirohydrochlorin. The tetrameric form of the protein is stabilized by Arg54 and Glu76, which form hydrogen bonds between two subunits. His96 is responsible for the binding of two haem groups within the main central cavity of the tetramer. Unexpectedly, CbiK P is shown to bind two additional haem groups through interaction with His103. Thus, although still retaining cobaltochelatase activity, the presence of His96 and His103 in CbiK P , which are absent from all other known bacterial cobaltochelatases, has evolved CbiK P a new function as a haem binding protein permitting it to act as a potential haem chaperone or transporter.

In Vitro Susceptibility of Sporothrix brasiliensis to Essential Oils of Lamiaceae Family - Stefanie Bressan Waller; Isabel Martins Madrid; Anna Luiza Silva; Luciana Laitano Dias de Castro; Marlete Brum Cleff; Vanny Ferraz; Mário Carlos Araújo Meireles; Régis Zanette; João Roberto Braga de Mello (Mycopathologia, 2016)

Correlation of proline content and gene expression involved in the metabolism of this amino acid under abiotic stress - Letícia Carvalho Benitez; Isabel Lopes Vighi; Priscila Ariane Auler; Marcelo Nogueira do Amaral; Gabriela Peres Moraes; Gabriela dos Santos Rodrigues; Luciano Carlos da Maia; Ariano Martins de Magalhães Júnior; Eugenia Jacira Bolacel Braga (Acta Physiologiae Plantarum, 2016)

Posaconazole plasma exposure correlated to intestinal mucositis in allogeneic stem cell transplant patients - Kim Vanstraelen; Juergen Prattes; Johan Maertens; Katrien Lagrou; Hélène Schoemans; Nele Peersman; Pieter Vermeersch; Koen Theunissen; Raf Mols; Patrick Augustijns; Pieter Annaert; Martin Hoenigl; et al. (European Journal of Clinical Pharmacology, 2016)

EPMA-World Congress 2015 - Jella-Andrea Abraham; Olga Golubnitschaja; Ildar Akhmetov; Russell J. Andrews; Leonidas Quintana; Russell J. Andrews; Babak Baban; Jun Yao Liu; Xu Qin; Tailing Wang; Mahmood S. Mozaffari; Viktoriia V. Bati; et al. (EPMA Journal, 2016)

Exome sequencing identifies potential novel candidate genes in patients with unexplained colorectal adenomatous polyposis - Isabel Spier; Martin Kerick; Dmitriy Drichel; Sukanya Horpaopan; Janine Altmüller; Andreas Laner; Stefanie Holzapfel; Sophia Peters; Ronja Adam; Bixiao Zhao; Tim Becker; Richard P. Lifton; et al. (Familial Cancer, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Exploring different strategies for imbalanced ADME data problem: case study on Caco-2 permeability modeling - Hai Pham-The; Gerardo Casañola-Martin; Teresa Garrigues; Marival Bermejo; Isabel González-Álvarez; Nam Nguyen-Hai; Miguel Ángel Cabrera-Pérez; Huong Le-Thi-Thu (Molecular Diversity, 2016)

Development of an autonomous system for integrated marine monitoring - Magalhães Catarina; Mucha Ana Paula; Carvalho Maria; Ribeiro Hugo; Almeida Cristina; Azevedo Isabel; Ramos Sandra; Borges Teresa; Leandro Sérgio; Dos Santos Antonina; Silva Alexandra; Bartilotti Cátia; et al. (Frontiers in Marine Science, 2016)

Long‐term elevated air [ CO 2 ] strengthens photosynthetic functioning and mitigates the impact of supra‐optimal temperatures in tropical Coffea arabica and C. canephora species - Weverton P. Rodrigues; Madlles Q. Martins; Ana S. Fortunato; Ana P. Rodrigues; José N. Semedo; Maria C. Simões‐Costa; Isabel P. Pais; António E. Leitão; Filipe Colwell; Luis Goulao; Cristina Máguas; Rodrigo Maia; et al. (Global Change Biology, 2016)
The tropical coffee crop has been predicted to be threatened by future climate changes and global warming. However, the real biological effects of such changes remain unknown. Therefore, this work aims to link the physiological and biochemical responses of photosynthesis to elevated air [ CO 2 ] and temperature in cultivated genotypes of C offea arabica L. (cv. Icatu and IPR 108) and Coffea canephora cv. Conilon CL 153. Plants were grown for ca. 10 months at 25/20 °C (day/night) and 380 or 700 μl CO 2 l −1 and then subjected to temperature increase (0.5 °C day −1 ) to 42/34 °C. Leaf impacts related to stomatal traits, gas exchanges, C isotope composition, fluorescence parameters, thylakoid electron transport and enzyme activities were assessed at 25/20, 31/25, 37/30 and 42/34 °C. The results showed that (1) both species were remarkably heat tolerant up to 37/30 °C, but at 42/34 °C a threshold for irreversible nonstomatal deleterious effects was reached. Impairments were greater in C. arabica (especially in Icatu) and under normal [ CO 2 ]. Photosystems and thylakoid electron transport were shown to be quite heat tolerant, contrasting to the enzymes related to energy metabolism, including RuBis CO , which were the most sensitive components. (2) Significant stomatal trait modifications were promoted almost exclusively by temperature and were species dependent. Elevated [ CO 2 ], (3) strongly mitigated the impact of temperature on both species, particularly at 42/34 °C, modifying the response to supra‐optimal temperatures, (4) promoted higher water‐use efficiency under moderately higher temperature (31/25 °C) and (5) did not provoke photosynthetic downregulation. Instead, enhancements in [ CO 2 ] strengthened photosynthetic photochemical efficiency, energy use and biochemical functioning at all temperatures. Our novel findings demonstrate a relevant heat resilience of coffee species and that elevated [ CO 2 ] remarkably mitigated the impact of heat on coffee physiology, therefore playing a key role in this crop sustainability under future climate change scenarios.

Induction of defence responses by cinnamomins against Phytophthora cinnamomi in Quercus suber and Quercus ilex subs. rotundifolia - Ghazal Ebadzad; Clara Medeira; Isabel Maia; Jorge Martins; Alfredo Cravador (European Journal of Plant Pathology, 2015)

Understanding fungal functional biodiversity during the mitigation of environmentally dispersed pentachlorophenol in cork oak forest soils - Adélia Varela; Celso Martins; Oscar Núñez; Isabel Martins; Jos A. M. P. Houbraken; Tiago M. Martins; M. Cristina Leitão; Iain McLellan; Walter Vetter; M. Teresa Galceran; Robert A. Samson; Andrew Hursthouse; et al. (Environmental Microbiology, 2015)
Summary Pentachlorophenol ( PCP ) is globally dispersed and contamination of soil with this biocide adversely affects its functional biodiversity, particularly of fungi – key colonizers. Their functional role as a community is poorly understood, although a few pathways have been already elucidated in pure cultures. This constitutes here our main challenge – elucidate how fungi influence the pollutant mitigation processes in forest soils. Circumstantial evidence exists that cork oak forests in N . W . T unisia – economically critical managed forests are likely to be contaminated with PCP , but the scientific evidence has previously been lacking. Our data illustrate significant forest contamination through the detection of undefined active sources of PCP . By solving the taxonomic diversity and the PCP ‐derived metabolomes of both the cultivable fungi and the fungal community, we demonstrate here that most strains (predominantly penicillia) participate in the pollutant biotic degradation. They form an array of degradation intermediates and by‐products, including several hydroquinone, resorcinol and catechol derivatives, either chlorinated or not. The degradation pathway of the fungal community includes uncharacterized derivatives, e.g. tetrachloroguaiacol isomers. Our study highlights fungi key role in the mineralization and short lifetime of PCP in forest soils and provide novel tools to monitor its degradation in other fungi dominated food webs.

Optical Fiber Technology for Monitoring and Preventing Biomass Washout from Bioreactors: a Case Study with a Sequencing Batch Reactor (SBR) - Flávio C. Silva; Martinho A. S. Martins; Lúcia Bilro; Rogério N. Nogueira; Isabel Capela; J. Jacob Keizer (Water, Air, & Soil Pollution, 2015)

Does 2‐phosphoglycolate serve as an internal signal molecule of inorganic carbon deprivation in the cyanobacterium S ynechocystis sp. PCC 6803? - Maya Haimovich‐Dayan; Judy Lieman‐Hurwitz; Isabel Orf; Martin Hagemann; Aaron Kaplan (Environmental Microbiology, 2015)
Summary Cyanobacteria possess CO 2 ‐concentrating mechanisms ( CCM ) that functionally compensate for the poor affinity of their ribulose‐1,5‐bisphosphate carboxylase/oxygenase ( R ubisco) to CO 2 . It was proposed that 2‐phosphoglycolate (2 PG ), produced by the oxygenase activity of R ubisco and metabolized via photorespiratory routes, serves as a signal molecule for the induction of CCM ‐related genes under limiting CO 2 level ( LC ) conditions. However, in vivo evidence is still missing. Since 2 PG does not permeate the cells, we manipulated its internal concentration. Four putative phosphoglycolate phosphatases ( PGP ases) encoding genes ( slr0458 , sll1349 , slr0586 and slr1762 ) were identified in the cyanobacterium S ynechocystis PCC 6803. Expression of slr0458 in E scherichia coli led to a significant rise in PGP ase activity. A S ynechocystis mutant overexpressing ( OE ) slr0458 was constructed. Compared with the wild type (WT), the mutant grew slower under limiting CO 2 concentration and the intracellular 2 PG level was considerably smaller than in the wild type, the transcript abundance of LC ‐induced genes including cmpA , sbtA and ndhF3 was reduced, and the OE cells acclimated slower to LC – indicated by the delayed rise in the apparent photosynthetic affinity to inorganic carbon. Data obtained here implicated 2 PG in the acclimation of this cyanobacterium to LC but also indicated that other, yet to be identified components, are involved.

Erratum to: New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2014)

Rates of spontaneous hybridization and hybrid recruitment in co-existing exotic and native mature larch populations - Patrick G. Meirmans; Marie-Claude Gros-Louis; Manuel Lamothe; Martin Perron; Jean Bousquet; Nathalie Isabel (Tree Genetics & Genomes, 2014)

Insights into the mechanisms underlying the antiproliferative potential of a Co(II) coordination compound bearing 1,10-phenanthroline-5,6-dione: DNA and protein interaction studies - Daniel V. Luís; Joana Silva; Ana Isabel Tomaz; Rodrigo F. M. de Almeida; Miguel Larguinho; Pedro V. Baptista; Luísa M. D. R. S. Martins; Telma F. S. Silva; Pedro M. Borralho; Cecília M. P. Rodrigues; António S. Rodrigues; Armando J. L. Pombeiro; et al. (JBIC Journal of Biological Inorganic Chemistry, 2014)

Candidiasis: Predisposing Factors, Prevention, Diagnosis and Alternative Treatment - Natália Martins; Isabel C. F. R. Ferreira; Lillian Barros; Sónia Silva; Mariana Henriques (Mycopathologia, 2014)

Broad-sense heritability in mixed models for grapevine initial selection trials - Elsa Gonçalves; Isabel Carrasquinho; António St. Aubyn; Antero Martins (Euphytica, 2013)

Influence of drought on tree rings and tracheid features of Pinus nigra and Pinus sylvestris in a mesic Mediterranean forest - Dario Martin-Benito; Hans Beeckman; Isabel Cañellas (European Journal of Forest Research, 2013)

Spatial–temporal patterns of flowering asynchrony and pollinator fidelity in hybridizing species of Narcissus - Isabel Marques; Javier Fuertes Aguilar; Maria Amélia Martins-Loução; Gonzalo Nieto Feliner (Evolutionary Ecology, 2012)

New polymorphisms in human MEF2C gene as potential modifier of hypertrophic cardiomyopathy - Cristina Alonso-Montes; Manuel Naves-Diaz; Jose Luis Fernandez-Martin; Julian Rodriguez-Reguero; Cesar Moris; Eliecer Coto; Jorge B. Cannata-Andia; Isabel Rodriguez (Molecular Biology Reports, 2012)

New mouse models for metabolic bone diseases generated by genome-wide ENU mutagenesis - Sibylle Sabrautzki; Isabel Rubio-Aliaga; Wolfgang Hans; Helmut Fuchs; Birgit Rathkolb; Julia Calzada-Wack; Christian M. Cohrs; Matthias Klaften; Hartwig Seedorf; Sebastian Eck; Ana Benet-Pagès; Jack Favor; et al. (Mammalian Genome, 2012)

Evolutionary trends in Hoplerythrinus unitaeniatus (Agassiz 1829) (Characiformes, Erythrinidae) - Renata da Rosa; Marceléia Rubert; Isabel Cristina Martins-Santos; Lucia Giuliano-Caetano (Reviews in Fish Biology and Fisheries, 2012)

Depth-dependent abundance of Midas Cichlid fish (Amphilophus spp.) in two Nicaraguan crater lakes - Marie Theres Dittmann; Marius Roesti; Adrian Indermaur; Marco Colombo; Martin Gschwind; Isabel Keller; Robin Kovac; Marta Barluenga; Moritz Muschick; Walter Salzburger (Hydrobiologia, 2012)

Epidemiological Findings and Laboratory Evaluation of Sporotrichosis: A Description of 103 Cases in Cats and Dogs in Southern Brazil - Isabel Martins Madrid; Antonella Souza Mattei; Cristina Gevehr Fernandes; Márcia de Oliveira Nobre; Mário Carlos Araújo Meireles (Mycopathologia, 2012)

Erratum to: Novel methods to induce exogenous gene expression in SCNT, parthenogenic and IVF preimplantation bovine embryos - Federico Pereyra-Bonnet; Romina Bevacqua; Isabel La Rosa; Pablo Sipowicz; Martin Radrizzani; Rafael Fernandez-Martin; Daniel Salamone (Transgenic Research, 2011)

Novel methods to induce exogenous gene expression in SCNT, parthenogenic and IVF preimplantation bovine embryos - Federico Pereyra-Bonnet; Romina Bevacqua; Isabel La Rosa; Pablo Sipowicz; Martin Radrizzani; Rafael Fernandez-Martin; Daniel Salamone (Transgenic Research, 2011)

Chromosome polymorphism in Rineloricaria pentamaculata (Loricariidae, Siluriformes) of the Paraná River basin - Fernanda Errero Porto; Ana Luiza de Brito Portela-Castro; Isabel Cristina Martins-Santos (Ichthyological Research, 2011)

Oxidative stress induced by cadmium in Nicotiana tabacum L.: effects on growth parameters, oxidative damage and antioxidant responses in different plant parts - Luisa Louro Martins; Miguel Pedro Mourato; Ana Isabel Cardoso; Ana Paula Pinto; Ana Maria Mota; Maria de Lurdes S. Gonçalves; Amarilis de Varennes (Acta Physiologiae Plantarum, 2011)

The removal of a disulfide bridge in CotA-laccase changes the slower motion dynamics involved in copper binding but has no effect on the thermodynamic stability - André T. Fernandes; Manuela M. Pereira; Catarina S. Silva; Peter F. Lindley; Isabel Bento; Eduardo Pinho Melo; Lígia O. Martins (JBIC Journal of Biological Inorganic Chemistry, 2011)

Using taxonomically unbiased criteria to prioritize resource allocation for oceanic island species conservation - José L. Martín; Pedro Cardoso; Manuel Arechavaleta; Paulo A. V. Borges; Bernardo F. Faria; Cristina Abreu; António F. Aguiar; José A. Carvalho; Ana C. Costa; Regina T. Cunha; Francisco M. Fernandes; Rosalina Gabriel; et al. (Biodiversity and Conservation, 2010)

Conservation Focus on Europe: Major Conservation Policy Issues That Need to Be Informed by Conservation Science - ANDREW S. PULLIN; ANDRÁS BÁLDI; OZGUN EMRE CAN; MARTIN DIETERICH; VASSILIKI KATI; BARBARA LIVOREIL; GABOR LÖVEI; BARBARA MIHÓK; OWEN NEVIN; NURIA SELVA; ISABEL SOUSA‐PINTO (Conservation Biology, 2009)
Europe is one of the world's most densely populated continents and has a long history of human‐dominated land‐ and seascapes. Europe is also at the forefront of developing and implementing multinational conservation efforts. In this contribution, we describe some top policy issues in Europe that need to be informed by high‐quality conservation science. These include evaluation of the effectiveness of the Natura 2000 network of protected sites, implications of rapid economic and subsequent land‐use change in Central and Eastern Europe, conservation of marine biodiversity and sustainability of fisheries, the effect of climate change on movement of species in highly fragmented landscapes, and attempts to assess the economic value of ecosystem services and biodiversity. Broad policy issues such as those identified are not easily amenable to scientific experiment. A key challenge at the science–policy interface is to identify the research questions underlying these problem areas so that conservation science can provide evidence to underpin future policy development .

Genome-wide search for genes that modulate inflammatory arthritis caused by Ali18 mutation in mice - Koichiro Abe; Matthias Klaften; Akira Narita; Tetsuaki Kimura; Kenji Imai; Minoru Kimura; Isabel Rubio-Aliaga; Sibylle Wagner; Thilo Jakob; Martin Hrabé de Angelis (Mammalian Genome, 2009)

Relevant principal component analysis applied to the characterisation of Portuguese heather honey - Rui C. Martins; Victor V. Lopes; Patrícia Valentão; João C.M.F. Carvalho; Paulo Isabel; Maria T. Amaral; Maria T. Batista; Paula B. Andrade; Branca M. Silva (Natural Product Research, 2008)

Occurrence of two cytotypes in Bryconamericus aff. iheringii (Characidae): karyotype analysis by C- and G-banding and replication bands - Ana Luiza de Brito Portela-Castro; Horácio Ferreira Julio; Isabel Cristina Martins dos Santos; Carla Simone Pavanelli (Genetica, 2008)

Effect of Polymer Strengtheners on the Local Environment of Biocompatible Glass as Probed by Fluorescence - Graham Hungerford; Mariana Amaro; Pedro Martins; M. Isabel Ferreira; Mahesh Uttamlal; A. Sheila Holmes-Smith (Journal of Fluorescence, 2008)

Effects of landscape structure and land‐use intensity on similarity of plant and animal communities - Carsten F. Dormann; Oliver Schweiger; Isabel Augenstein; Debra Bailey; Regula Billeter; Geert De Blust; Riccardo DeFilippi; Mark Frenzel; Frederik Hendrickx; Felix Herzog; Stefan Klotz; Jaan Liira; et al. (Global Ecology and Biogeography, 2007)
Aim Species richness in itself is not always sufficient to evaluate land management strategies for nature conservation. The exchange of species between local communities may be affected by landscape structure and land‐use intensity. Thus, species turnover, and its inverse, community similarity, may be useful measures of landscape integrity from a diversity perspective. Location A European transect from France to Estonia. Methods We measured the similarity of plant, bird, wild bee, true bug, carabid beetle, hoverfly and spider communities sampled along gradients in landscape composition (e.g. total availability of semi‐natural habitat), landscape configuration (e.g. fragmentation) and land‐use intensity (e.g. pesticide loads). Results Total availability of semi‐natural habitats had little effect on community similarity, except for bird communities, which were more homogeneous in more natural landscapes. Bee communities, in contrast, were less similar in landscapes with higher percentages of semi‐natural habitats. Increased landscape fragmentation decreased similarity of true bug communities, while plant communities showed a nonlinear, U‐shaped response. More intense land use, specifically increased pesticide burden, led to a homogenization of bee, bug and spider communities within sites. In these cases, habitat fragmentation interacted with pesticide load. Hoverfly and carabid beetle community similarity was differentially affected by higher pesticide levels: for carabid beetles similarity decreased, while for hoverflies we observed a U‐shaped relationship. Main conclusions Our study demonstrates the effects of landscape composition, configuration and land‐use intensity on the similarity of communities. It indicates reduced exchange of species between communities in landscapes dominated by agricultural activities. Taxonomic groups differed in their responses to environmental drivers and using but one group as an indicator for ‘biodiversity’ as such would thus not be advisable.

Yeasts in high Arctic glaciers: the discovery of a new habitat for eukaryotic microorganisms - Lorena Butinar; Isabel Spencer-Martins; Nina Gunde-Cimerman (Antonie van Leeuwenhoek, 2007)

Imaging viral infection: studies on Nicotiana benthamiana plants infected with the pepper mild mottle tobamovirus - María Luisa Pérez-Bueno; Massimo Ciscato; Martin vandeVen; Isabel García-Luque; Roland Valcke; Matilde Barón (Photosynthesis Research, 2007)

A Study of Protein Electrochemistry on a Supported Membrane Electrode - Adam Mechler; Gayathri Nawaratna; Marie-Isabel Aguilar; Lisandra L. Martin (International Journal of Peptide Research and Therapeutics, 2006)

Arbuscular mycorrhizal fungi enhance root cadmium and copper accumulation in the roots of the salt marsh plant Aster tripolium L. - Luís M. Carvalho; Isabel Caçador; M. Amélia Martins-Loução (Plant and Soil, 2006)

Perturbations of the T1 copper site in the CotA laccase from Bacillus subtilis: structural, biochemical, enzymatic and stability studies - Paulo Durão; Isabel Bento; André T. Fernandes; Eduardo P. Melo; Peter F. Lindley; Lígia O. Martins (JBIC Journal of Biological Inorganic Chemistry, 2006)

Sexual reproduction, clonal diversity and genetic differentiation in patchily distributed populations of the temperate forest herb Paris quadrifolia (Trilliaceae) - Hans Jacquemyn; Rein Brys; Olivier Honnay; Martin Hermy; Isabel Roldán-Ruiz (Oecologia, 2006)

Local forest environment largely affects below‐ground growth, clonal diversity and fine‐scale spatial genetic structure in the temperate deciduous forest herb Paris quadrifolia - HANS JACQUEMYN; REIN BRYS; OLIVIER HONNAY; MARTIN HERMY; ISABEL ROLDÁN‐RUIZ (Molecular Ecology, 2005)
Paris quadrifolia (herb Paris) is a long‐lived, clonal woodland herb that shows strong differences in local population size and shoot density along an environmental gradient of soil and light conditions. This environmentally based structuring may be mediated by differences in clonal growth and seedling recruitment through sexual reproduction. To study the interrelationship between environmental conditions and spatial patterns of clonal growth, the spatial genetic structure of four P. quadrifolia populations growing in strongly contrasting sites was determined. In the first place, plant excavations were performed in order to (i) determine differences in below‐ground growth of genets, (ii) investigate connectedness of ramets and (iii) determine total genet size. Although no differences in internode length were found among sites, clones in moist sites were much smaller (genets usually consisted of 1–3 interconnected shoots, most of them flowering) than genets in dry sites, which consisted of up to 15 interconnected shoots, the majority of which were vegetative. Further, amplified fragment length polymorphism (AFLP) markers were used. Clonal diversity was higher in populations located in moist and productive ash–poplar forests compared to those found in drier and less productive mixed forest sites ( G / N : 0.27 and 0.14 and Simpson's D : 0.84 and 0.75, respectively). Patterns of spatial population genetic structure under dry conditions revealed several large clones dominating the entire population, whereas in moist sites many small genets were observed. Nevertheless, strong spatial genetic structure of the genet population was observed. Our results clearly demonstrate that patterns of clonal diversity and growth form of P. quadrifolia differ among environments. Limited seedling recruitment and large clone sizes due to higher connectedness of ramets explain the low clonal diversity in dry sites. In moist sites, higher levels of clonal diversity and small clone sizes indicate repeated seedling recruitment, whereas strong spatial genetic structure suggests limited seed dispersal within populations.

Intracellular S-adenosylhomocysteine increased levels are associated with DNA hypomethylation in HUVEC - Rita Castro; Isabel Rivera; Carla Martins; Eduard A. Struys; Erwin E. W. Jansen; Nuno Clode; Luís M. Graça; Henk J. Blom; Cornelis Jakobs; Isabel Tavares de Almeida (Journal of Molecular Medicine, 2005)

Palaeoindian occupation of the Atacama Desert, northern Chile - Martin Grosjean; Lautaro Núñez; Isabel Cartajena (Journal of Quaternary Science, 2005)
Palaeoindian occupation of the Atacama Desert in northern Chile has been found between 12 600 and 10 200 cal. yr BP. The new site at Salar Punta Negra (24°28′S/60°53′W/2976 m) includes about 1000 classifiable, mostly unifacial artefacts and, uniquely, three different diagnostic types of early projectile points. Two of the Lateglacial/early Holocene projectile types have wide distribution and are known from different geographical areas in South America: the Palaeoindian ‘Fell’ fish‐tail point mainly from the southern cone of South America, and the triangular ‘Tuina’ points typical of the Puna of the south‐central Andes in northern Chile and northwestern Argentina. In addition, we found a third type, a stemmed point typical for the Salar Punta Negra. Filling a large geographical gap of ‘Fell’ occupation, the site at Salar Punta Negra provides evidence for generally much higher mobility and diversity of early cultures, and supports an Andean‐Pacific route for early human exploration of South America to the south through the desert at intermediate altitudes. Contemporaneous high‐amplitude climatic changes were fundamental preconditions to provide adequate environments and habitats, and to make Palaeoindian hunting‐gathering occupation possible in the Atacama Desert. Copyright © 2005 John Wiley & Sons, Ltd.

Sympatric occurrence of three cytotypes and four morphological types of B chromosomes of Astyanax scabripinnis (Pisces, Characiformes) in the River Ivaí Basin, state of Paraná, Brazil - Carlos Alexandre Fernandes; Isabel Cristina Martins-Santos (Genetica, 2005)

The role of 5-HT in the impairment of thermoregulation observed in rats administered MDMA (‘ecstasy’) when housed at high ambient temperature - Kathryn S. Saadat; Esther O’Shea; M. Isabel Colado; J. Martin Elliott; A. Richard Green (Psychopharmacology, 2005)

Hyperthermic and neurotoxic effect of 3,4-methylenedioxymethamphetamine (MDMA) in guinea pigs - A. Richard Green; Kathryn S. Saadat; J. Martin Elliott; M. Isabel Colado (Psychopharmacology, 2004)

Effect of ambient temperature and a prior neurotoxic dose of 3,4-methylenedioxymethamphetamine (MDMA) on the hyperthermic response of rats to a single or repeated (‘binge’ ingestion) low dose of MDMA - A. Richard Green; Veronica Sanchez; Esther O’Shea; Kathryn S. Saadat; J. Martin Elliott; M. Isabel Colado (Psychopharmacology, 2004)

Comparison of phenotypic and genotypic taxonomic methods for the identification of dairy enterococci - Paula Isabel Alves; Maria Paula Martins; Teresa Semedo; José Joaquim Figueiredo Marques; Rogério Tenreiro; Maria Teresa Barreto Crespo (Antonie van Leeuwenhoek, 2004)

Role of A β and the α 7 nicotinic acetylcholine receptor in regulating synaptic plasticity in Alzheimer's disease - David H. Small; Lisa R. Fodero; Dusan Losic; Cindy Chu; Marie-Isabel Aguilar; Lisandra L. Martin; Mary Chebib (International Journal of Peptide Research and Therapeutics, 2003)

A 2-Opt Tabu Search Procedure for the Multiperiod Forest Harvesting Problem with Adjacency, Greenup, Old Growth, and Even Flow Constraints - Felipe Caro; Miguel Constantino; Isabel Martins; Andrés. Weintraub (Forest Science, 2003)
Because of environmental concerns, modern forest harvesting plans are being modified to address aesthetics and wildlife protection issues. In the literature, the most referenced are adjacency constraints with exclusion or “greenup” years. Also of interest are the concepts of old growth patch size and total old growth area restrictions. Typically, harvest blocks have been defined a priori. Recently, some have proposed a more complex approach in which basic cells are defined, and the decision-making process includes forming harvest blocks from these cells. This has been called ARM (Area Restriction Model). Until now, no successful exact method has been reported for large-scale ARM problems, leaving heuristics as a viable option. In this work we present a multiperiod harvest-scheduling ARM model with these spatial constraints. A tabu search procedure with 2-Opt moves (exchanging at most 2 units) was developed. For small size instances, the procedure found the optimal solution in most cases, and for a real-size problem an 8% optimality gap is provided.

Effects of salinity and flooding on the infectivity of salt marsh arbuscular mycorrhizal fungi in Aster tripolium L. - Lus M. Carvalho; Patrcia M. Correia; Isabel Caador; M. Amlia Martins-Louo (Biology and Fertility of Soils, 2003)

A Natural Triploid in Trichomycterus Davisi (Siluriformes, Trichomycteridae): Mitotic and Meiotic Characterization by Chromosome Banding and Synaptonemal Complex Analyses - Luciana Andreia Borin; Isabel Cristina Martins-Santos; Claudio Oliveira (Genetica, 2002)

Temporal and spatial variation of arbuscular mycorrhizas in salt marsh plants of the Tagus estuary (Portugal) - Luís M. Carvalho; Isabel Caçador; M. Martins-Loução (Mycorrhiza, 2001)

Karyotype characterization of three species of the genus Trichomycterus (Teleostei, Siluriformes) from Iguaçu river basin - Luciana Andreia Borin; Isabel Cristina Martins-Santos (Genetica, 1999)

Fungemia in cancer patients in Brazil: Predominance of non-albicans species - Marcio Nucci; Maria Isabel Silveira; Nelson Spector; Fernanda Silveira; Eduardo Velasco; Carlos Alberto Martins; Andrea Derossi; Arnaldo L. Colombo; Wolmar Pulcheri (Mycopathologia, 1998)

Myxozyma kluyveri sp. nov. (Candidaceae)—a new species from Southern Africa - J. P. Van Der Walt; Isabel Spencer-Martins; Y. Yamada; P. D. G. Richards (Antonie van Leeuwenhoek, 1989)